Curable composition
By using a blending technology of aliphatic isocyanate compounds, hydroxide fillers and plasticizers in thermal conduction polymers, the problems of increased viscosity, poor stability and high specific gravity during storage and use of existing thermal conduction polymers are solved, and a curable composition with low density, high thermal conductivity and excellent blending characteristics are achieved.
Patent Information
- Application Number
- CN202380042723.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-25
- Filing Date
- 2023-05-25
- Publication Date
- 2025-03-04
AI Technical Summary
During storage and use of existing thermally conductive polymers, there are problems of increased viscosity, poor stability and high specific gravity, making it difficult to achieve low density, excellent blending characteristics and high thermal conductivity at the same time.
Aliphatic isocyanate compounds are blended with hydroxide filler and plasticizer, and by adjusting the molecular weight and component ratio of the isocyanate compounds, combining an appropriate amount of hydroxide filler and plasticizer, a curable composition with low density, high thermal conductivity and excellent blending characteristics are formed.
The curable composition is achieved with low density, excellent maintenance stability and storage stability, and cured products with high thermal conductivity, low specific gravity and relatively high hardness after curing.
Smart Images

Figure BDA0005151366370000221 
Figure BDA0005151366370000222 
Figure BDA0005151366370000411
Abstract
Description
Technical Field
[0001] This application claims priority to Korean Patent Application No. 10-2022-0064080, filed on May 25, 2022, the disclosure of which is incorporated herein by reference in its entirety.
[0002] The present invention relates to curable compositions and their use. Background Art
[0003] According to the progress of ultra-high speed and miniaturization technology, the devices or machines applied to the technology require higher power and faster speed. Such high power and fast speed cause more heat to be generated during the operation process, thereby increasing the demand for thermal conductive materials with heat dissipation effect, which can effectively dissipate and / or remove heat.
[0004] For example, Patent Document 1 discloses a material in which a thermally conductive filler is blended with a polymer, and such a material is applied to a battery module.
[0005] Polyurethane is used as a polymer blended with a thermally conductive filler. A composition forming such a material can be formed by reacting a main portion containing a polyol compound with a curing agent portion containing an isocyanate compound.
[0006] However, in such a composition, the isocyanate group of the curing agent part particularly exhibits high reactivity with moisture, so that problems such as viscosity increase over time occur. Therefore, for such a composition, it is necessary to ensure so-called storage stability or retention stability.
[0007] In addition, for heat dissipation performance, a relatively excessive amount of thermally conductive fillers is included in such compositions. Typically, oxide fillers such as alumina are used as such fillers. Such fillers have excellent thermal conductivity but have a high specific gravity, making them an obstacle to making the material lighter.
[0008] For example, hydroxide fillers such as aluminum hydroxide have low specific gravity and thermal conductivity. However, such fillers have thermal conductivity, but their thermal conductivity characteristics are not as good as those of oxide fillers. In addition, hydroxide fillers have hydroxyl groups, wherein such hydroxyl groups can react with moisture or isocyanate groups of curing agents. Therefore, if an excessive amount of hydroxide fillers is used, it is difficult to ensure storage stability and retention stability, blending characteristics are also reduced, and thermal conductivity cannot be stably ensured.
[0009] Furthermore, hydroxide fillers have relatively low hardness, making them also unsuitable for forming materials requiring high hardness.
[0010] <Prior Art Literature>
[0011] <Patent Documents>
[0012] (Patent Document 1) Korean Patent Publication No. 10-2021-0042969 Summary of the invention
[0013] Technical issues
[0014] The application provides curable composition and its use. The application can provide such curable composition and its use, and the curable composition is conducive to the reduction of weight by showing low density, and has excellent retention stability and storage stability by suppressing the change of viscosity over time. In addition, the curable composition can show excellent blending characteristics during the manufacturing process, and forms a cured product with high thermal conductivity, low specific gravity (density) and relatively high hardness when solidified. The application is also intended to provide a device comprising a curable composition or its cured product.
[0015] Technical Solution
[0016] Among the physical properties mentioned in the present application, unless otherwise specifically stated, the physical properties whose measurement temperature affects the results are the physical properties measured at room temperature.
[0017] Among the physical properties mentioned in this application, unless otherwise specifically stated, the physical properties measuring the pressure-affected results are the physical properties measured under normal pressure conditions.
[0018] Among the physical properties mentioned in this application, unless otherwise specifically stated, the physical properties measuring the effect of humidity are the physical properties measured under normal humidity conditions.
[0019] In this specification, the term room temperature means a natural temperature without heating or cooling. For example, room temperature may be any temperature in the range of 10°C to 30°C, and may mean a temperature of about 23°C or about 25°C. Unless otherwise specified, the unit of temperature mentioned in this specification is Celsius (°C).
[0020] In the present specification, normal pressure means natural pressure without pressurization or decompression. For example, normal pressure may generally mean about 1 atmosphere at the atmospheric pressure level.
[0021] In this specification, the term normal humidity means natural humidity without special adjustment under room temperature and normal pressure conditions. For example, normal humidity may mean any humidity in the range of about 20RH% to 80RH% or 40RH% to 60RH%. Here, the unit RH% (relative humidity%) used is a unit expressed as a percentage of the current amount of water vapor if the maximum amount of water vapor that can be contained at a specific temperature is set to 100.
[0022] In this specification, the terms weight-average molecular weight (Mw) and number-average molecular weight (Mn) mean the molecular weights to be measured using GPC (gel permeation chromatography), and the unit thereof is g / mol. In addition, the term polydispersity index (PDI) as used in this specification is a value (Mw / Mn) obtained by dividing the weight-average molecular weight (Mw) by the number-average molecular weight (Mn). The number-average molecular weight (Mn) and the weight-average molecular weight (Mw) can be measured by diluting the sample to a concentration of about 20 mg / mL with THF (tetrahydrofuran) after placing the sample in a 20 mL vial, and then filtering the standard sample for calibration and the sample to be measured through a syringe filter (pore size: 0.2 μm). ChemStation of Agilent technologies can be used as the analysis program, and the number-average molecular weight (Mn) and the weight-average molecular weight (Mw) can be obtained by comparing the elution time of the sample with the calibration curve.
[0023] <GPC measurement conditions>
[0024] Instrument: 1200 series of Agilent technologies
[0025] Column: TL Mix.A&B of Agilent technologies is used
[0026] Solvent: THF
[0027] Column temperature: 40 °C
[0028] Sample concentration: 20 mg / mL, 10 μl injection
[0029] MP: 364000, 91450, 17970, 4910, 1300 are used as the standard samples
[0030] As used herein, the term curing means a phenomenon in which the hardness or viscosity of a material increases through a physical reaction and / or a chemical reaction.
[0031] As used herein, the term curability means that a material is capable of curing.
[0032] In this specification, the term substituent means an atom or a group of atoms that replaces a hydrogen atom present in any compound. In addition, the substituents are described as follows, but are not limited thereto, and unless otherwise specified herein, the substituents may be further substituted with the substituents described below or may not be substituted with any substituents.
[0033] In this specification, unless otherwise described, the term alkyl can be a linear or branched alkyl or alkylene group having 1 to 20 carbon atoms, or 1 to 16 carbon atoms, or 1 to 12 carbon atoms, or 1 to 8 carbon atoms, or 1 to 6 carbon atoms, or can be a cyclic alkyl group having 3 to 20 carbon atoms, or 3 to 16 carbon atoms, or 3 to 12 carbon atoms, or 3 to 8 carbon atoms, or 3 to 6 carbon atoms. Here, cyclic alkyl also includes alkyl groups having only a ring structure and alkyl groups containing a ring structure. For example, cyclohexyl and methylcyclohexyl both correspond to cyclic alkyl groups. Furthermore, for example, the alkyl group can be specifically exemplified by a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a tert-butyl group, a sec-butyl group, a 1-methyl-butyl group, a 1-ethyl-butyl group, an n-pentyl group, an isopentyl group, a neopentyl group, a tert-pentyl group, an n-hexyl group, a 1-methylpentyl group, a 2-methylpentyl group, a 4-methyl-2-pentyl group, a 3,3-dimethylbutyl group, a 2-ethylbutyl group, an n-heptyl group, a 1-methylhexyl group, an n-octyl group, a tert-octyl group, a 1-methylheptyl group, a 2-ethylhexyl group, a 2-propylpentyl group, an n-nonyl group, a 2,2-dimethylheptyl group, a 1-ethylpropyl group, a 1,1-dimethylpropyl group, an isohexyl group, a 2-methylpentyl group, a 4-methylhexyl group, a 5-methylhexyl group, and the like, but is not limited thereto. In addition, the cycloalkyl group or the cycloalkylene group can be specifically exemplified by cyclopropyl, cyclobutyl, cyclopentyl, 3-methylcyclopentyl, 2,3-dimethylcyclopentyl, cyclohexyl, 3-methylcyclohexyl, 4-methylcyclohexyl, 2,3-dimethylcyclohexyl, 3,4,5-trimethylcyclohexyl, 4-tert-butylcyclohexyl, cycloheptyl, cyclooctyl, etc., but are not limited thereto.
[0034] In this specification, unless otherwise described, the term alkenyl or alkenylene can be a linear or branched acyclic alkenyl or alkenylene having 2 to 20 carbon atoms, or 2 to 16 carbon atoms, or 2 to 12 carbon atoms, or 2 to 8 carbon atoms, or 2 to 6 carbon atoms, or a cyclic alkenyl or alkenylene having 3 to 20 carbon atoms, or 3 to 16 carbon atoms, or 3 to 12 carbon atoms, or 3 to 8 carbon atoms, or 3 to 6 carbon atoms. Here, when alkenyl or alkenylene having a ring structure is included, it corresponds to a cyclic alkenyl or alkenylene. In addition, for example, it can be exemplified by vinylene, n-propenylene, isopropenylene, n-butenylene, isobutenylene, tert-butenylene, sec-butenylene, 1-methyl-butenylene, 1-ethyl-butenylene, n-pentenylene, isopentenylene, neopentenylene, tert-pentenylene, n-hexenylene, 1-methylpentenylene, 2-methylpentenylene, 4-methyl-2-pentenylene, 3,3-dimethylpentenylene, butenyl, 2-ethylbutenyl, n-heptenyl, 1-methylhexenyl, n-octenyl, tert-octenyl, 1-methylheptenyl, 2-ethylhexenyl, 2-propylpentenyl, n-nonenyl, 2,2-dimethylheptenyl, 1-ethylpropenyl, 1,1-dimethylpropenyl, isohexenyl, 2-methylpentenyl, 4-methylhexenyl, 5-methylhexenyl, etc., but are not limited thereto. In addition, the cycloalkenyl group or cycloalkenylene group can be specifically exemplified by cyclopropenyl, cyclobutenyl, cyclopentenyl, 3-methylcyclopentenyl, 2,3-dimethylcyclopentenyl, cyclohexenyl, 3-methylcyclohexenyl, 4-methylcyclohexenyl, 2,3-dimethylcyclohexenyl, 3,4,5-trimethylcyclohexenyl, 4-tert-butylcyclohexenyl, cycloheptenyl, cyclooctenyl, etc., but are not limited thereto.
[0035] In this specification, unless otherwise described, the term alkynyl or alkynylene can be a linear or branched acyclic alkynyl or alkynylene having 2 to 20 carbon atoms, or 2 to 16 carbon atoms, or 2 to 12 carbon atoms, or 2 to 8 carbon atoms, or 2 to 6 carbon atoms, or can be a cyclic alkynyl or alkynylene having 3 to 20 carbon atoms, or 3 to 16 carbon atoms, or 3 to 12 carbon atoms, or 3 to 8 carbon atoms, or 3 to 6 carbon atoms. Herein, when an alkynyl or alkynylene having a ring structure is included, it corresponds to a cyclic alkynyl or alkynylene. In addition, for example, it can be exemplified by an ethynyl group, a n-propynyl group, an isopropynyl group, a n-butynyl group, an isobutynyl group, a tert-butynyl group, a sec-butynyl group, a 1-methyl-butynyl group, a 1-ethyl-butynyl group, a n-pentynyl group, an isopentenyl group, a neopentynyl group, a tert-pentynyl group, a n-hexynyl group, a 1-methylpentynyl group, a 2-methylpentynyl group, a 4-methyl-2-pentynyl group, a 3,3-dimethylpentynyl group, a butynyl, 2-ethylbutynyl, n-heptynyl, 1-methylhexynyl, n-octynyl, tert-octynyl, 1-methylheptynyl, 2-ethylhexynyl, 2-propylpentynyl, n-nonynyl, 2,2-dimethylheptynyl, 1-ethylpropynyl, 1,1-dimethylpropynyl, isohexynyl, 2-methylpentynyl, 4-methylhexynyl, 5-methylhexynyl, etc., but are not limited thereto. In addition, the cycloalkynyl group or cycloalkynylene group can be specifically exemplified by cyclopropynyl, cyclobutynyl, cyclopentynyl, 3-methylcyclopentynyl, 2,3-dimethylcyclopentynyl, cyclohexynyl, 3-methylcyclohexynyl, 4-methylcyclohexynyl, 2,3-dimethylcyclohexynyl, 3,4,5-trimethylcyclohexynyl, 4-tert-butylcyclohexynyl, cycloheptynyl, cyclooctynyl, etc., but are not limited thereto.
[0036] In the present specification, unless otherwise specified, the term alkoxy group may mean a linear or branched alkoxy group having 1 to 20 carbon atoms, or 1 to 16 carbon atoms, or 1 to 12 carbon atoms, or 1 to 8 carbon atoms, or 1 to 6 carbon atoms, or 1 to 4 carbon atoms, or may mean a cyclic alkoxy group having 3 to 20 carbon atoms, or 3 to 16 carbon atoms, or 3 to 12 carbon atoms, or 3 to 8 carbon atoms, or 3 to 6 carbon atoms.
[0037] In the present specification, the terms alkylidene and alkylene both mean a divalent residue formed by removing two hydrogen atoms from an alkane. However, an alkylidene group means a divalent residue formed by removing two hydrogen atoms from one carbon atom of an alkane, and an alkylene group means a divalent residue formed by removing one hydrogen atom from each of two different carbon atoms of an alkane.
[0038] In the present specification, unless otherwise specified, the term alkylidene group may mean a linear or branched alkylidene group having 1 to 20 carbon atoms, or 1 to 16 carbon atoms, or 1 to 12 carbon atoms, or 1 to 8 carbon atoms, or 1 to 6 carbon atoms, or 1 to 4 carbon atoms, or may mean a cyclic alkylidene group having 3 to 20 carbon atoms, or 3 to 16 carbon atoms, or 3 to 12 carbon atoms, or 3 to 8 carbon atoms, or 3 to 6 carbon atoms.
[0039] In the present specification, unless otherwise specified, the term alkylene may mean a linear or branched alkylene group having 2 to 20 carbon atoms, or 2 to 16 carbon atoms, or 2 to 12 carbon atoms, or 2 to 8 carbon atoms, or 2 to 6 carbon atoms, or 2 to 4 carbon atoms, or may mean a cyclic alkylene group having 3 to 20 carbon atoms, or 3 to 16 carbon atoms, or 3 to 12 carbon atoms, or 3 to 8 carbon atoms, or 3 to 6 carbon atoms.
[0040] Alkyl, alkylene, alkoxy, alkylidene, alkenyl, alkenylene, alkynyl and alkynylene may also be optionally substituted with one or more substituents. In this case, the substituent may be one or more selected from the group consisting of halogen (chlorine (Cl), iodine (I), bromine (Br), fluorine (F)), aryl, heteroaryl, epoxy, alkoxy, cyano, carboxyl, acryloyl, methacryloyl, acryloyloxy, methacryloyloxy, carbonyl, and hydroxyl, but is not limited thereto.
[0041] In this specification, the term aryl means an aromatic ring wherein one hydrogen is removed from an aromatic hydrocarbon ring, wherein the aromatic hydrocarbon ring may include a monocyclic or polycyclic ring. Unless otherwise described, aryl does not have a particularly limited number of carbon atoms, but may be an aryl having 6 to 30 carbon atoms, or 6 to 26 carbon atoms, or 6 to 22 carbon atoms, or 6 to 20 carbon atoms, or 6 to 18 carbon atoms, or an aryl having 6 to 18 carbon atoms, or 6 to 15 carbon atoms. In addition, in this specification, the term arylidene means that aryl has two bonding positions, i.e., a divalent group. The description of aryl as described above may be applied, except that these are each a divalent group. Aryl may be exemplified as, for example, phenyl, phenylethyl, phenylpropyl, benzyl, tolyl, xylyl or naphthyl, but is not limited thereto.
[0042] In this specification, the term heteroaryl is an aromatic ring comprising one or more heteroatoms other than carbon, which may specifically include one or more heteroatoms selected from nitrogen (N), oxygen (O), sulfur (S), selenium (Se) and tellurium (Te). In this case, the atom constituting the ring structure of heteroaryl can be referred to as ring atoms. In addition, heteroaryl can include monocycle or polycycle. Unless otherwise described, heteroaryl does not have a particularly restricted number of carbon atoms, but can be a heteroaryl with 2 to 30 carbon atoms, or 2 to 26 carbon atoms, or 2 to 22 carbon atoms, or 2 to 22 carbon atoms, or 2 to 20 carbon atoms, or 2 to 18 carbon atoms, or 2 to 15 carbon atoms. In another example, heteroaryl does not have a particularly restricted number of ring atoms, but can be a heteroaryl with 5 to 30, 5 to 25, 5 to 20, 5 to 15, 5 to 10 or 5 to 8 ring atoms. The heteroaryl group can be exemplified by, for example, thienyl, furyl, pyrrolyl, imidazolyl, thiazolyl, Azolyl, oxadiazolyl, triazolyl, pyridyl, bipyridyl, pyrimidyl, triazinyl, acridinyl, pyridazinyl, pyrazinyl, quinolyl, quinazolinyl, quinoxalinyl, phthalazinyl, pyridopyrimidinyl, pyridopyrazinyl, pyrazinopyrazinyl, isoquinolyl, indolyl, carbazolyl, benzo oxazolyl, benzimidazolyl, benzothiazolyl, benzocarbazolyl, dibenzocarbazolyl, benzothiophenyl, dibenzothiophenyl, benzofuranyl, dibenzofuranyl, benzothiorolyl, dibenzothiorolyl, phenanthroline, isothiophene Azolyl, thiadiazolyl, phenothiazinyl, phen Azine group and its condensed structure, etc., but are not limited thereto.
[0043] In the present specification, the term heteroarylene means that a heteroaryl group has two bonding positions, that is, a divalent group. The description of the heteroaryl group as described above can be applied, except that each of these is a divalent group.
[0044] The aryl, arylene, heteroarylene or heteroaryl group may also be optionally substituted with one or more substituents. In this case, the substituent may be one or more selected from the following: halogen (chlorine (Cl), iodine (I), bromine (Br), fluorine (F)), aryl, heteroaryl, epoxy, alkoxy, cyano, carboxyl, acryloyl, methacryloyl, acryloyloxy, methacryloyloxy, carbonyl, and hydroxyl, but is not limited thereto.
[0045] In this specification, the term amine group means a functional group in which two hydrogen atoms or substituents are bonded to a nitrogen atom with a non-shared electron pair. Amine groups can be divided into primary amine groups in which two hydrogen atoms are bonded to a nitrogen atom with a non-shared electron pair, secondary amine groups in which one hydrogen atom and one substituent are bonded to a nitrogen atom with a non-shared electron pair, and tertiary amine groups in which two substituents are bonded to a nitrogen atom with a non-shared electron pair. At this time, the substituent can be selected from one or more of the following: alkyl, alkenyl, alkynyl, halogen (chlorine (Cl), iodine (I), bromine (Br), and fluorine (F)), aryl, heteroaryl, epoxy, alkoxy, cyano, carboxyl, acryloyl, methacryloyl, acryloyloxy, methacryloyloxy, carbonyl, and hydroxyl, but are not limited thereto.
[0046] The curable composition may include an isocyanate compound, a filler component, and a plasticizer.
[0047] In this specification, the term curable composition means a composition that can be cured. The curable composition may include components commonly referred to as polymers and components that can be converted into polymers by physical or chemical reactions such as curing or polymerization. The curable composition may have so-called adhesive properties and / or pressure-sensitive adhesive properties before or after curing.
[0048] The curable composition can be a solvent-based curable composition, a water-based curable composition or a solvent-free curable composition. In addition, the curable composition can be an active energy ray (e.g., ultraviolet) curable type, a moisture curable type, a thermosetting type, or a room temperature curable type. When the curable composition is an active energy ray curable type, the curing of the curable composition can be carried out by irradiating active energy rays such as ultraviolet rays; in the case of a moisture curable type, the curing of the curable composition can be carried out by a method of keeping it under appropriate moisture; in the case of a thermosetting type, the curing of the curable composition can be carried out by a method of applying appropriate heat; or in the case of a room temperature curable type, the curing of the curable composition can be carried out by a method of keeping the curable composition at room temperature.
[0049] The curable composition according to one example of the present application may be a one-component curable composition or a two-component curable composition, and in some cases, it may be any part of the two-component curable composition.
[0050] As is known, the term one-component curable composition as used in the present application means a composition in which all components required for curing are present in a mixed state and are cured when certain conditions are met (e.g., a specific temperature or ultraviolet irradiation, etc.). In addition, the term two-component curable composition as used in the present application means a composition in which the components required for curing are present in a physically separated state (e.g., separated into a main part and a curing agent part), and the separated components are mixed and exposed to a curable environment to be cured.
[0051] The curable composition according to an example of the present application may include an isocyanate compound as described above. In this specification, the term isocyanate compound may mean a compound with one or more isocyanate groups. In this specification, the term diisocyanate compound may mean a compound with two or more isocyanate groups. In this specification, the term polyisocyanate compound may mean a compound with three or more isocyanate groups. The lower limit of the number of isocyanate groups in the polyisocyanate compound may be 3, and the upper limit thereof may be 10, 9, 8, 7, 6, 5, 4 or 3. The number of isocyanate groups may be in a range greater than or equal to, or greater than any one of the above lower limits; in a range less than or equal to, or less than any one of the above upper limits; or in a range less than or equal to, or less than any one of the above upper limits and greater than or equal to, or greater than any one of the above lower limits.
[0052] The isocyanate compound is not particularly limited, and those commonly used in the industry (for example, those generally used for forming polyurethane) can be used. For example, as the diisocyanate compound, an aromatic diisocyanate compound such as toluene diisocyanate, diphenylmethane diisocyanate, phenylene diisocyanate, polyethylene phenylene polyisocyanate, xylene diisocyanate, tetramethylxylene diisocyanate, triazine diisocyanate, naphthalene diisocyanate and / or triphenylmethane triisocyanate can be used; and / or an aliphatic diisocyanate compound including a chain diisocyanate compound such as hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, lysine diisocyanate, methyl norbornane diisocyanate, ethylene diisocyanate, propylene diisocyanate and / or tetramethylene diisocyanate; and an alicyclic diisocyanate compound such as trans-cyclohexane-1,4-diisocyanate, isophorone diisocyanate, bis(isocyanatemethyl)cyclohexane diisocyanate and / or dicyclohexylmethane diisocyanate, etc. can be used. As the diisocyanate compound, one of the above-mentioned types or a mixture of two or more thereof may be used.
[0053] As the polyisocyanate compound, one or more selected from the following can be used: isocyanates in the form of adding one or two or more of the above-mentioned diisocyanate compounds to a polyol compound, a polymer complex of a diisocyanate compound, and a biuret compound thereof. For example, an aromatic polyisocyanate compound, which is an adduct of an aromatic diisocyanate compound with a polyol, a polymer complex, or a biuret compound; and / or an aliphatic polyisocyanate compound, which is an adduct of an aliphatic diisocyanate compound with a polyol, a polymer complex, and / or a biuret compound, etc. can be used. As the polyisocyanate compound, one or a mixture of two or more of the above types can be used.
[0054] In a curable composition according to an example of the present application, an aliphatic isocyanate compound may be used as the isocyanate compound. The isocyanate compound of the curable composition may not contain an aromatic isocyanate compound, and may contain only an aliphatic isocyanate compound. By using only an aliphatic isocyanate compound as the isocyanate compound, when it is blended with a filler component to be described below, while having excellent blending properties, it can be beneficial to ensure a physical property with a small viscosity change caused by changes over time.
[0055] The isocyanate compound of the curable composition according to an example of the present application may include a diisocyanate compound and a polyisocyanate compound. When the diisocyanate compound and the polyisocyanate compound are mixed and used in a suitable ratio, when it is blended with the filler component to be described below, while having excellent blending characteristics, it can be beneficial to ensure that there is a small physical property of viscosity change caused by time change. Here, the diisocyanate compound can be an aliphatic diisocyanate compound, and the polyisocyanate compound can be an aliphatic polyisocyanate compound. Through this combination, when it is blended with the filler component to be described below, while having excellent blending characteristics, it can be beneficial to ensure that there is a small physical property of viscosity change caused by time change. In this specification, the term aliphatic diisocyanate compound can mean a diisocyanate compound that does not contain any aromatic functional group in its molecular structure, and the term aliphatic polyisocyanate compound can mean a polyisocyanate compound that does not contain any aromatic functional group in its molecular structure. Examples of aliphatic diisocyanate compounds and aliphatic polyisocyanate compounds are as described above.
[0056] The molecular weight or weight average molecular weight of the diisocyanate compound contained in the isocyanate compound of the curable composition according to one example of the present application may be 100g / mol, 110g / mol, 120g / mol, 130g / mol, 140g / mol, 150g / mol, 160g / mol, or 170g / mol, and the upper limit thereof may be 300g / mol, 280g / mol, 260g / mol, 240g / mol, 220g / mol, 200g / mol, or 180g / mol. The molecular weight or weight average molecular weight may be in the range of greater than or equal to, or greater than any one of the above lower limits; in the range of less than or equal to, or less than any one of the above upper limits; or in the range of less than or equal to, or less than any one of the above upper limits and greater than or equal to, or greater than any one of the above lower limits.
[0057] In addition, the molecular weight or weight average molecular weight of the polyisocyanate compound contained in the curable composition according to one example of the present application may be 600g / mol, 620g / mol, 640g / mol, 660g / mol, 680g / mol, 700g / mol, 720g / mol, 740g / mol, 760g / mol, 780g / mol, or 800g / mol, and the upper limit thereof may be 1,000g / mol, 980g / mol, 960g / mol, 940g / mol, 920g / mol, 900g / mol, 880g / mol, 860g / mol, or 840g / mol. The molecular weight or weight average molecular weight may be in a range greater than or equal to, or greater than any one of the above lower limits; in a range less than or equal to, or less than any one of the above upper limits; or in a range less than or equal to, or less than any one of the above upper limits and greater than or equal to, or greater than any one of the above lower limits. When such a component is blended with a filler component to be described below, it can be advantageous to ensure physical properties having small viscosity changes due to changes over time while having excellent blending properties. Here, the molecular weight or weight average molecular weight can be measured by the above-mentioned GPC.
[0058] When the isocyanate compound contains both a diisocyanate compound and a polyisocyanate compound, the lower limit of the weight ratio of the polyisocyanate compound relative to 100 parts by weight of the diisocyanate compound may be 1 part by weight, 10 parts by weight, 20 parts by weight, 30 parts by weight, 40 parts by weight, 50 parts by weight, 60 parts by weight, 70 parts by weight, 80 parts by weight, 90 parts by weight, or about 100 parts by weight, and the upper limit thereof may be about 1000 parts by weight, 900 parts by weight, 800 parts by weight, 700 parts by weight, 600 parts by weight, 500 parts by weight, 400 parts by weight, 300 parts by weight, 200 parts by weight, 150 parts by weight, or about 100 parts by weight. The weight ratio may be in the range of greater than or equal to, or greater than any one of the above lower limits; in the range of less than or equal to, or less than any one of the above upper limits; or in the range of less than or equal to, or less than any one of the above upper limits and greater than or equal to, or greater than any one of the above lower limits.
[0059] The curable composition according to one example of the present application may include a filler component as described above. Through the filler component, thixotropy and / or heat dissipation (thermal conductivity) within the battery module or battery pack can be ensured as needed during the process. The term filler component means a component consisting only of a filler.
[0060] According to one example of the present application, the lower limit of the weight ratio of the filler component in the curable composition can be about 70 wt%, 70 wt%, 71 wt%, 72 wt%, 73 wt%, 74 wt%, 75 wt%, 76 wt%, 77 wt%, 78 wt%, 79 wt%, 80 wt%, 81 wt%, 82 wt%, 83 wt%, 84 wt%, 85 wt%, 86 wt%, or 87 wt%, and the upper limit thereof can be about 99 wt%, 98 wt%, 97 wt%, 96 wt%, 95 wt%, 94 wt%, 93 wt%, 92 wt%, 91 wt%, 90 wt%, 89 wt%, 88 wt%, or 87 wt%. The weight ratio may be within a range greater than or equal to, or greater than any of the above lower limits; within a range less than or equal to, or less than any of the above upper limits; or within a range less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.
[0061] The filler component of the curable composition according to an example of the present application may include a thermally conductive filler, or may be a thermally conductive filler component. The term thermally conductive filler component or thermally conductive filler means a filler component or filler when the curable composition or its cured product exhibits a thermal conductivity described below through a related filler. The thermal conductivity of such a filler or filler component may be, for example, about 1 W / m·K or greater, about 5 W / m·K or greater, about 10 W / m·K or greater, or about 15 W / m·K or greater, or may be about 400 W / m·K or less, about 350 W / m·K or less, or about 300 W / m·K or less.
[0062] The thermal conductive filler may include an oxide filler such as aluminum oxide (aluminum oxide), magnesium oxide, beryllium oxide or titanium oxide; a nitride filler such as boron nitride, silicon nitride or aluminum nitride; a carbide filler such as silicon carbide; a hydroxide filler such as aluminum hydroxide or magnesium hydroxide; a metal filler such as copper, silver, iron, aluminum or nickel; a metal alloy filler such as titanium; or silicon powder such as quartz, glass or silicon dioxide, etc., but is not limited thereto. In addition, in consideration of ensuring insulation properties, the application of carbon fillers such as graphite or activated carbon may also be considered.
[0063] The filler component of the curable composition according to an example of the present application can use one or two or more appropriately selected as needed, and the form or ratio is not particularly limited, and it can be selected considering the viscosity of the curable composition, the possibility of sedimentation in the cured product, the desired heat resistance or thermal conductivity, insulation, filling effect or dispersibility, etc. In addition, even if the same type of filler is used, a mixture of fillers with different shapes can be used, and a mixture of fillers with different average particle sizes can also be used. For example, a mixture of aluminum hydroxide, aluminum and aluminum oxide can be used, wherein their respective shapes and average particle sizes can be different from each other.
[0064] In this specification, the term average particle size is a so-called D50 particle size (median particle size), which may mean a particle size at 50% of the cumulative volume basis of the particle size distribution. That is, the particle size distribution may be obtained based on the volume, and the average particle size may be regarded as a particle size at a point where the cumulative value is 50% in a cumulative curve where the total volume is set to 100%. Such a D50 particle size may be measured by a laser diffraction method.
[0065] Meanwhile, the shape of the filler included in the filler component of the curable composition of an example of the present application can be appropriately selected from spherical shape and / or non-spherical shape (for example, rectangular shape and needle-like shape, etc.), and used as required, but not limited thereto. In this specification, the term spherical filler means a filler having a sphericity of about 0.9 or greater or 0.95 or greater, and a non-spherical or rectangular filler means a filler having a sphericity less than 0.95 or less than 0.9. Sphericity can be determined by the particle shape analysis of the filler. Specifically, the sphericity of the filler for three-dimensional particles can be defined as the ratio (S' / S) of the surface area (S) of the sphere with the same volume of filler and the surface area (S) of the filler. For actual fillers, circularity is generally used. Circularity is expressed as the ratio of the boundary of a circle with the same image and the same area (A) as the two-dimensional image of the actual filler thus obtained to the boundary (P) of the image, which is obtained by the following equation.
[0066] <Circularity equation>
[0067] Circularity = 4πA / P 2
[0068] The circularity is expressed as a value from 0 to 1, where a perfect circle has a value of 1, and when the particles have an irregular shape, the value is less than 1. The sphericity value in the present application is considered to be the average value of the circularity measured with a particle shape analysis device (FPIA-3000) from Marvern.
[0069] The filler component of the curable composition according to an example of the application can basically comprise hydroxide filler to achieve the purpose.Such filler is favourable in weight reduction because it is the filler of relatively low specific gravity.For example, based on the gross weight of filler component, the lower limit of the weight ratio of hydroxide filler can be 30 % by weight, 32 % by weight, 34 % by weight, 36 % by weight, 38 % by weight, 40 % by weight, 42 % by weight, 44 % by weight, 46 % by weight, 48 % by weight, 50 % by weight, 52 % by weight, 54 % by weight, 56 % by weight, 58 % by weight or about 60 % by weight, and its upper limit can be 80 % by weight, 78 % by weight, 76 % by weight, 74 % by weight, 72 % by weight, 70 % by weight, 68 % by weight, 66 % by weight, 64 % by weight or about 62 % by weight. The weight ratio may be within a range greater than or equal to, or greater than any of the above lower limits; within a range less than or equal to, or less than any of the above upper limits; or within a range less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.
[0070] The upper limit of the specific gravity of the hydroxide filler at room temperature may be about 3, 2.9, 2.8, 2.7, 2.6 or 2.5, and the lower limit thereof may be about 1. The specific gravity may be in a range greater than or equal to, or greater than any of the above lower limits; in a range less than or equal to, or less than any of the above upper limits; or in a range less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.
[0071] Since the filler component includes the hydroxide filler having the above-mentioned specific gravity range in the content ratio range, low density characteristics and excellent blending characteristics can be ensured. The hydroxide filler may be a thermally conductive filler, examples of which are as described above.
[0072] The filler component of the curable composition according to an example of the present application may include a first hydroxide filler and a second hydroxide filler with different average particle sizes as hydroxide fillers. For example, the lower limit of the average particle size of the first hydroxide filler may be about 60 μm, 61 μm, 62 μm, 63 μm, 64 μm, 65 μm, 66 μm, 67 μm, 68 μm, 69 μm, or 70 μm, and its upper limit may be about 200 μm, 190 μm, 180 μm, 170 μm, 160 μm, or 150 μm. The average particle size may be greater than or equal to, or greater than any one of the above lower limits; less than or equal to, or less than any one of the above upper limits; or less than or equal to, or less than any one of the above upper limits and greater than or equal to, or greater than any one of the above lower limits. In addition, the upper limit of the average particle size of the second hydroxide filler can be about 10μm, 9μm, 8μm, 7μm, 6μm, 5μm, 4μm, 3μm, or 2μm, and its lower limit can be about 0.01μm, 0.05μm, 0.1μm, or 0.5μm. The average particle size can be greater than or equal to, or greater than any one of the above lower limits; less than or equal to, or less than any one of the above upper limits; or less than or equal to, or less than any one of the above upper limits and greater than or equal to, or greater than any one of the above lower limits. As described above, since the filler component of the curable composition includes two hydroxide fillers with different average particle sizes, excellent blending characteristics can be ensured. In one example, the first hydroxide filler can be a filler with the largest average particle size among all the hydroxide fillers contained in the filler component, and the second hydroxide filler can be a filler with the smallest average particle size among all the hydroxide fillers contained in the filler component.
[0073] The filler component of the curable composition according to one example of the present application may include a first hydroxide filler and a second hydroxide filler as hydroxide fillers, and the weight ratio (HF1 / HF2) of the first hydroxide filler (HF1) to the second hydroxide filler (HF2) may have a lower limit of about 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, or 2, and an upper limit thereof may be about 10, 9.5, 9, 8.5, 8, 7.5, 7, 6.5, 6, 5.5, 5, 4.5, 4, 3.5, 3, 2.5, or 2. The weight ratio may be in a range of greater than or equal to, or greater than any of the above lower limits; in a range of less than or equal to, or less than any of the above upper limits; or in a range of less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits. Since the filler component of the curable composition includes two hydroxide fillers having different average particle sizes in the above weight ratio, excellent blending characteristics can be ensured.
[0074] The filler component of the curable composition according to one example of the present application may include a first hydroxide filler and a second hydroxide filler as hydroxide fillers, and the lower limit of the average particle size ratio (DHF1 / DHF2) of the first hydroxide filler (DHF1) to the second hydroxide filler (DHF2) may be about 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, or 30, and the upper limit thereof may be about 100, 95, 90, 85, 80, 75, 70, 65, 60, 55, 50, 49, 48, 47, 46, 45, 44, 43, 42, 41, 40, 39, 38, 37, 36, or 35. The ratio may be within a range of greater than or equal to, or greater than any of the above lower limits; within a range of less than or equal to, or less than any of the above upper limits; or within a range of less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits. Since the filler component of the curable composition includes two hydroxide fillers having different average particle sizes at the above average particle size ratio, excellent blending characteristics can be ensured.
[0075] The filler component of the curable composition according to an example of the application can also include non-hydroxide filler (or can also be referred to as other filler) and hydroxide filler to achieve the purpose.Term non-hydroxide filler means a filler that is not a hydroxide.As other filler, one or more selected from oxide filler, nitride filler, carbide filler, metal filler, alloy filler, silicon powder and carbon filler can be used, and their specific types are as described above.
[0076] In one example, the lower limit of the content of the non-hydroxide filler in the filler component relative to 100 parts by weight of the hydroxide filler can be about 10 parts by weight, 15 parts by weight, 20 parts by weight, 25 parts by weight, 30 parts by weight, 35 parts by weight, 40 parts by weight, 45 parts by weight, 50 parts by weight, 55 parts by weight, 60 parts by weight, or 65 parts by weight, and the upper limit thereof can be about 200 parts by weight, 190 parts by weight, 180 parts by weight, 170 parts by weight, 160 parts by weight, 150 parts by weight, 140 parts by weight, 130 parts by weight, 120 parts by weight, 110 parts by weight, 100 parts by weight, 90 parts by weight, 80 parts by weight, or 70 parts by weight. The ratio can be in the range of greater than or equal to, or greater than any one of the above lower limits; in the range of less than or equal to, or less than any one of the above upper limits; or in the range of less than or equal to, or less than any one of the above upper limits and greater than or equal to, or greater than any one of the above lower limits.
[0077] The lower limit of the room temperature specific gravity of the non-hydroxide filler can be about 3, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, or 3.9, and the upper limit thereof can be about 10. The specific gravity can be in a range greater than or equal to, or greater than any one of the above lower limits; in a range less than or equal to, or less than any one of the above upper limits; or in a range less than or equal to, or less than any one of the above upper limits and greater than or equal to, or greater than any one of the above lower limits. Since the filler component contains additional fillers in the above content ratio range, thixotropy, hardness viscosity and thermal conductivity characteristics suitable for the process can be ensured. The additional filler can be a thermally conductive filler, examples of which are as described above.
[0078] The filler component of the curable composition according to one example of the present application may also include additional fillers and hydroxide fillers at the same time to achieve the purpose, and the additional filler may be selected from one or more of oxide fillers, nitride fillers, carbide fillers, metal fillers, alloy fillers, silicon powders and carbon fillers, and when included, the average particle size of the additional filler may be in the range of 10 μm to 60 μm. For example, the lower limit of the weight ratio (HF1 / AF) of the first hydroxide filler (HF1) to the additional filler (AF) in the filler component may be about 0.5, 0.6, 0.7, 0.8, 0.9 or 1, and the upper limit thereof may be about 20, 18, 16, 14, 12, 10, 8, 6, 4, 2, 1.5 or 1. The ratio may be in the range of greater than or equal to, or greater than any one of the above lower limits; in the range of less than or equal to, or less than any one of the above upper limits; or in the range of less than or equal to, or less than any one of the above upper limits and greater than or equal to, or greater than any one of the above lower limits. Since the filler component also contains another filler having the average particle size, and at the same time the weight ratio with the first hydroxide filler satisfies the above range, thixotropy, viscosity and thermal conductivity characteristics suitable for the process can be ensured. In addition, the lower limit of the average particle size ratio (DHF1 / DAF) of the first hydroxide filler (DHF1) to the other filler (DAF) in the filler component can be about 1, 1.2, 1.4, 1.6, 1.8, 2, 2.2, 2.4, 2.6, 2.8, 3, 3.2, or 3.4, and the upper limit thereof can be about 5, 4.8, 4.6, 4.4, 4.2, 4, 3.8, or 3.6. The ratio can be greater than or equal to, or greater than any one of the above lower limits; less than or equal to, or less than any one of the above upper limits; or less than or equal to, or less than any one of the above upper limits and greater than or equal to, or greater than any one of the above lower limits. Since the filler component further contains another filler having the above average particle diameter and at the same time the average particle diameter ratio with the first hydroxide filler satisfies the above range, thixotropy, viscosity and thermal conductivity characteristics suitable for the process can be ensured.
[0079] In one example, when the filler component comprises a hydroxide filler (DHF) and an additional filler (DAF), the ratio (A / B) of the average particle size (A) of the hydroxide filler (DHF) to the average particle size (B) of the additional filler may have a lower limit of about 1, 1.2, 1.4, 1.6, 1.8, 2, 2.1, 2.2, or 2.3, and an upper limit thereof may be about 5, 4.8, 4.6, 4.4, 4.2, 4, 3.8, 3.6, 3.4, 3.2, 3.0, 2.8, 2.6, 2.5, or 2.5. The ratio may be in a range greater than or equal to, or greater than any of the above lower limits; in a range less than or equal to, or less than any of the above upper limits; or in a range less than or equal to, or less than any of the above upper limits while greater than or equal to, or greater than any of the above lower limits. Here, the average particle size of the hydroxide filler and the additional filler is the weighted average of the respective average particle sizes. For example, if the filler component contains a filler (A) having an average particle size of D1 and a filler (B) having an average particle size of D2 as the hydroxide filler, and the weight ratio between the fillers is W1:W2 (A:B), the weighted average value can be calculated as (D1×W1+D2×W2) / (W1+W2), which is also the same for the additional filler. Since the filler component further contains the additional filler having the average particle size, and at the same time the average particle size ratio with the hydroxide filler satisfies the above range, thixotropy, viscosity and thermal conductivity characteristics suitable for the process can be ensured.
[0080] As mentioned above, the curable composition according to an example of the present application may include a plasticizer. According to the curable composition of an example of the present application, a plasticizer may be included in an appropriate ratio to improve the storage stability and the problem of the deterioration of the blending characteristics caused by the isocyanate group and moisture and / or the hydroxyl group of the filler component present in the isocyanate compound. As mentioned above, by including the plasticizer of an appropriate ratio, it is possible to ensure that there is a low viscosity increase rate due to time variation and a curable composition of excellent blending characteristics. In addition, although a plasticizer is applied, a cured product with an appropriate hardness can also be formed.
[0081] In a curable composition according to one example of the present application, as a plasticizer, one or more selected from the following can be used: phthalic acid compounds, phosphoric acid compounds, adipic acid compounds, sebacic acid compounds, citric acid compounds, glycolic acid compounds, trimellitic acid compounds, polyester compounds, epoxidized soybean oil, chlorinated paraffin, chlorinated fatty acid esters, fatty acid compounds and vegetable oils. For example, as the phthalate compound, one or more of the following can be used: dimethyl phthalate, diethyl phthalate, dibutyl phthalate, dihexyl phthalate, di-n-octyl phthalate, di-2-ethylhexyl phthalate, diisooctyl phthalate, dioctyl phthalate, dinonyl phthalate, diisononyl phthalate, didecyl phthalate, diundecyl phthalate, dilauryl phthalate, ditridecyl phthalate, dibenzyl phthalate, dicyclohexyl phthalate, butyl benzyl phthalate, octyl decyl phthalate, butyl octyl phthalate, octyl benzyl phthalate, n-hexyl-n-decyl phthalate, n-octyl phthalate and n-decyl phthalate. In addition, as the phosphoric acid compound, one or more of the following can be used: tricresyl phosphate, trioctyl phosphate, triphenyl phosphate, octyl diphenyl phosphate, cresyl diphenyl phosphate, and trichloroethyl phosphate. In addition, as the adipic acid compound, one or more of the following can be used: dibutoxyethoxyethyl adipate (DBEEA), dioctyl adipate, diisooctyl adipate, di-n-octyl adipate, didecyl adipate, diisodecyl adipate, dinonyl adipate, diisononyl adipate, n-octyl n-decyl adipate, n-heptyl adipate, and n-nonyl adipate. In addition, as the sebacic acid compound, one or more of dibutyl sebacate, dioctyl sebacate, diisooctyl sebacate, and butylbenzyl ester can be used. In addition, as the citric acid compound, one or more of triethyl citrate, acetyl triethyl citrate, tributyl citrate, acetyl tributyl citrate, and acetyl trioctyl citrate can be used. In addition, as the glycolic acid compound, one or more of methyl phthaloyl ethyl glycolate, ethyl phthaloyl ethyl glycolate, and butyl phthaloyl ethyl glycolate can be used. In addition, as the trimellitic acid compound, one or more of trioctyl trimellitate and tri-n-octyl-n-decyl trimellitate can be used.
[0082] In consideration of the purpose of the present application, the curable composition according to one example of the present application may include a combination of an isocyanate compound and a filler component, and one or more selected from a phthalic acid compound and an adipic acid compound as a plasticizer.
[0083] In order to achieve appropriate effects, non-reactive ester compounds from the above-mentioned types may be used as plasticizers. The term non-reactive means that the compound does not react with the isocyanate compound contained in the curable composition, and the ester compound means a compound having at least one ester bond.
[0084] The lower limit of the number of ester bonds contained in the non-reactive ester compound may be about 1 or 2, and the upper limit thereof may be about 10, 9, 8, 7, 6, 5, 4, 3, or 2. The number of ester bonds may be in a range greater than or equal to, or greater than any of the above lower limits; in a range less than or equal to, or less than any of the above upper limits; or in a range less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.
[0085] In addition, in the non-reactive ester compound, one end of the ester bond may be connected to the aromatic structure. In this case, the lower limit of the number of carbons in the aromatic structure may be 6, and the upper limit may be about 20, 18, 16, 14, 12, 10, 8 or 6. The number of carbons may be in a range greater than or equal to, or greater than any of the above lower limits; in a range less than or equal to, or less than any of the above upper limits; or in a range less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.
[0086] In the non-reactive ester compound, the other end of the ester bond (the other end not connected to the aromatic structure) can be connected to an alkyl, alkenyl or alkynyl. At this time, the lower limit of the carbon number of each alkyl, alkenyl or alkenyl can be 6, 7, 8 or 9, and its upper limit can be about 30, 28, 26, 24, 22, 20, 18, 16, 14, 12 or 10. The carbon number can be greater than or equal to or greater than any one of the above lower limits; less than or equal to or less than any one of the above upper limits; or less than or equal to or less than any one of the above upper limits and greater than or equal to or greater than any one of the above lower limits. Alkyl, alkenyl or alkynyl can be linear, branched or cyclic, and can be appropriately linear or branched or branched.
[0087] The molecular weight (molar mass or weight average molecular weight) of the non-reactive ester compound may have a lower limit of 200 g / mol, 250 g / mol, 300 g / mol, 350 g / mol, or 400 g / mol, and an upper limit thereof may be about 2000 g / mol, 1500 g / mol, 1000 g / mol, 900 g / mol, 800 g / mol, 700 g / mol, 600 g / mol, 500 g / mol, or 450 g / mol. The molecular weight may be in a range greater than or equal to, or greater than any of the above lower limits; in a range less than or equal to, or less than any of the above upper limits; or in a range less than or equal to, or less than any of the above upper limits while greater than or equal to, or greater than any of the above lower limits. The alkyl, alkenyl or alkynyl group may be linear, branched or cyclic, and may be linear or branched or branched as appropriate.
[0088] The lower limit of the weight ratio of the plasticizer relative to 100 parts by weight of the isocyanate compound may be about 0.1 parts by weight, 0.5 parts by weight, 1 part by weight, 1.5 parts by weight, 2 parts by weight, 2.5 parts by weight, 3 parts by weight, 3.5 parts by weight, 4 parts by weight, 4.5 parts by weight, or 5 parts by weight, and the upper limit thereof may be 15 parts by weight, 14.5 parts by weight, 14 parts by weight, 13.5 parts by weight, 13 parts by weight, 12.5 parts by weight, 12 parts by weight, 11.5 parts by weight, 11 parts by weight, 10.5 parts by weight, or 10 parts by weight. The ratio may be in the range of greater than or equal to, or greater than any one of the above lower limits; in the range of less than or equal to, or less than any one of the above upper limits; or in the range of less than or equal to, or less than any one of the above upper limits and greater than or equal to, or greater than any one of the above lower limits. When the plasticizer in the curable composition is adjusted to the above content ratio, a cured product having excellent surface hardness and thermal conductivity can be ensured, and a curable composition having a low viscosity increase rate due to changes over time and excellent blending characteristics can be ensured.
[0089] In a curable composition according to an example of the present application, the lower limit of the weight ratio of the plasticizer relative to 100 parts by weight of the filler component may be about 0.1 parts by weight, 0.15 parts by weight, 0.2 parts by weight, 0.25 parts by weight, 0.3 parts by weight, 0.35 parts by weight, 0.4 parts by weight, 0.45 parts by weight, or about 0.5 parts by weight, and the upper limit thereof may be about 1.5 parts by weight, 1.45 parts by weight, 1.4 parts by weight, 1.35 parts by weight, 1.3 parts by weight, 1.2 parts by weight, 1.15 parts by weight, or about 1.1 parts by weight. The ratio may be in a range greater than or equal to, or greater than any one of the above lower limits; in a range less than or equal to, or less than any one of the above upper limits; or in a range less than or equal to, or less than any one of the above upper limits and greater than or equal to, or greater than any one of the above lower limits. When the plasticizer in the curable composition is adjusted to the above content ratio, a cured product having excellent surface hardness and thermal conductivity can be ensured, and a curable composition having a low viscosity increase rate due to changes over time and excellent blending characteristics can be ensured.
[0090] In a curable composition according to an example of the present application, the lower limit of the weight ratio of the plasticizer relative to 100 parts by weight of the hydroxide filler in the filler component can be about 0.5 parts by weight, 0.55 parts by weight, 0.6 parts by weight, 0.65 parts by weight, 0.7 parts by weight, 0.75 parts by weight, 0.8 parts by weight, 0.85 parts by weight, or about 0.9 parts by weight, and the upper limit thereof can be about 10 parts by weight, 9 parts by weight, 8 parts by weight, 7 parts by weight, 6 parts by weight, 5 parts by weight, 4 parts by weight, 3 parts by weight, or about 2 parts by weight. The ratio can be in a range greater than or equal to, or greater than any one of the above lower limits; in a range less than or equal to, or less than any one of the above upper limits; or in a range less than or equal to, or less than any one of the above upper limits and greater than or equal to, or greater than any one of the above lower limits. In consideration of the combination with the hydroxide filler, when the plasticizer in the curable composition is adjusted to the above content ratio, a cured product having excellent surface hardness and thermal conductivity can be ensured, and a curable composition having a low viscosity increase rate due to changes over time and excellent blending characteristics can be ensured.
[0091] The curable composition according to one example of the present application can help ensure the desired physical properties by further comprising additional compounds (if necessary). Since the additional compounds include one or more of those mentioned below, the present application can help ensure the desired physical properties.
[0092] If necessary, the curable composition according to an example of the present application may also include a viscosity modifier, for example, a thixotropy imparting agent, a diluent, a surface treatment agent or a coupling agent, etc., for viscosity adjustment, such as viscosity increase or decrease, or for viscosity adjustment according to shear force. The thixotropy imparting agent can adjust the viscosity of the curable composition according to the shear force. Available thixotropy imparting agents can be exemplified as pyrogenic silica, etc. The diluent is generally used to reduce the viscosity of the curable composition, wherein if various types known in the industry can show such an effect, they can be used without restriction. The surface treatment agent is used to treat the surface of the filler introduced into the curable composition, wherein if various types known in the industry can show such an effect, they can be used without restriction. In the case of a coupling agent, for example, it can be used to improve the dispersibility between the filler component and other components, and if various types known in the industry can show such an effect, they can be used without restriction. In addition, if necessary, the curable composition according to an example of the present application may also include a flame retardant or a flame retardant aid, etc. The curable composition also including a flame retardant or a flame retardant aid can be cured to form a flame retardant resin. Flame retardant is not particularly limited, and various known flame retardants can be applied, for example, solid filler type flame retardant or liquid flame retardant can be applied. Flame retardant includes, for example, organic flame retardant such as melamine cyanurate / ester or inorganic flame retardant such as magnesium hydroxide, etc., but is not limited thereto. If the amount of thermally conductive filler contained in the curable composition is large, liquid flame retardant material (TEP, triethyl phosphate, or TCPP, tris (1,3-chloro-2-propyl) phosphate, etc.) can also be used. In addition, a silane coupling agent that can act as a flame retardant synergist can also be added. In addition, if necessary, a curable composition according to an example of the present application can also further use a dispersant to improve dispersibility, wherein various types of dispersants known in the art can be used without restriction, for example, polyester dispersants can be used. In addition, if necessary, a curable composition according to an example of the present application can use a hygroscopic agent, wherein if the hygroscopic agent is intended to minimize the effect of the isocyanate compound on moisture, it can be used without restriction, for example, a siloxane compound can be used.
[0093] In a curable composition according to an example of the present application, the upper limit of the density measured at room temperature (about 25° C.) can be about 2.5 g / mL, 2.49 g / mL, 2.48 g / mL, 2.47 g / mL, 2.46 g / mL, 2.45 g / mL, 2.44 g / mL, 2.43 g / mL, 2.42 g / mL, 2.41 g / mL, or about 2.4 g / mL, and its lower limit can be about 1 g / mL. The density can be less than or equal to, or less than any one of the above upper limits; or less than or equal to, or less than any one of the above upper limits while being greater than or equal to, or greater than any one of the above lower limits. Since the curable composition combines the isocyanate compound, filler component and plasticizer as described above, the low density property can be ensured as described above. In addition, specifically, the density can be measured according to the density measurement part in the embodiment to be described below.
[0094] The curable composition according to one example of the present application may have a viscosity change rate (V R ). For example, the viscosity change rate V R The upper limit may be about 15%, 14%, 13%, 12%, 11%, 10%, 9%, 8%, 7%, 6%, 5%, 4.9%, 4.8%, 4.7%, 4.6%, or 4.5%, and the lower limit may be about 0%, 1%, 2%, 3%, 4%, or 5%. The viscosity change rate may be in the range of less than or equal to, or less than any of the above upper limits; or in the range of less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.
[0095] [General equation 1]
[0096] V R =100×|V f -V i | / V i
[0097] In the general equation 1, V i is the initial viscosity of the curable composition measured at room temperature at a shear rate of 1.2 rpm, and V f To measure V i The viscosity of the curable composition measured at a shear rate of 1.2 rpm at room temperature after the curable composition was kept at room temperature for 240 hours starting from the time point of . The method for measuring the viscosity is described in the Examples section of the present specification.
[0098] By combining the isocyanate compound, filler component and plasticizer as described above, as described above, the curable composition can have a low viscosity change rate over time. The curable composition according to one example of the present application contains an excess of hydroxide filler to ensure low density characteristics, but based on the appropriate combination of isocyanate compound and plasticizer, it can have a low viscosity change rate caused by changes over time.
[0099] The curable composition according to an example of the present application can be formed by mixing the individual components listed above. In addition, if all necessary components can be included, the mixing order of the curable composition according to an example of the present application is not particularly limited. However, when the filler component and the isocyanate compound are blended, this can be carried out by first blending filler particles with a minimum average particle size to prepare a primary mixture, and further blending filler particles with average particle sizes of different sizes in the primary mixture to prepare a secondary mixture.
[0100] Specifically, the method for preparing a curable composition according to an example of the present application may include the following steps: mixing an isocyanate compound, a second hydroxide filler and a plasticizer to prepare a primary mixture; and further adding and mixing the first hydroxide filler to the primary mixture to prepare a secondary mixture. Here, in the step of preparing the secondary mixture, the first hydroxide filler and another filler may also be added to the primary mixture.
[0101] When the curable composition is prepared in the above manner, the phenomenon of mixing between the filler component and the isocyanate compound and agglomeration between filler particles in the filler component can be minimized.
[0102] The curable composition according to another example of the present application includes a main part containing a polyol compound; and a curing agent part, wherein the curing agent part can be a curable composition according to an example of the present application as described above, or can include the composition. Here, in order to distinguish the curable composition according to another example of the present application from the curable composition according to an example of the present application, the curable composition according to another example of the present application can be considered as a curable composition mixed with the main part. Since the curing agent part includes a curable composition according to an example of the present application as described above, the details will be omitted.
[0103] The curable composition mixed with the main part according to one example of the present application may include a component generally referred to as a resin and a component that can be converted into a resin by a curing reaction or a polymerization reaction, which itself may have adhesive or pressure-sensitive adhesive properties, and may have adhesive or pressure-sensitive adhesive properties by a reaction such as a curing reaction.
[0104] Meanwhile, the curable composition mixed with the main part according to an example of the present application can be a solvent-based curable composition, a water-based curable composition, or a solvent-free curable composition, and can be an active energy ray (e.g., ultraviolet) curable type, a moisture curable type, a heat curable type, or a room temperature curable type. Considering the purpose of the present application, it may be suitable that the curable composition mixed with the main part is a solvent-free type and / or a room temperature curable type.
[0105] The term polyol compound as used in the present application may refer to a compound having two or more hydroxyl groups at the end of its chemical structure. More specifically, a compound having two hydroxyl groups may be referred to as a diol, and a compound having three hydroxyl groups may be referred to as a triol. In the curable composition mixed with the main part according to one example of the present application, the polyol compound contained in the main part is not particularly limited as long as it meets the above definition. For example, (poly)ethylene glycol, diethylene glycol, (poly)propylene glycol, 1,2-butanediol, 2,3-butanediol, 1,3-propylene glycol, 1,3-butanediol, 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, 1,2-ethylhexyl glycol, 1,5-pentanediol, 1,9-nonanediol, 1,10-decanediol, 1,3-cyclohexanedimethanol and 1,4-cyclohexanedimethanol, (poly)ethylene glycol, diethylene glycol, (poly)propylene glycol, glycerol, 1,2,3-butanetriol, 1,2,4-butanetriol, 1,3,4-hexanetriol, 1,3,6-hexanetriol unit and trimethylolpropane can be used. In addition, in another example, the polyol compound contained in the main part can include polyester polyol. Polyester polyol can include carboxylic acid-based polyol and / or caprolactone-based polyol. Here, carboxylic acid-based polyol can be a polyol compound represented by the following formula 1, and caprolactone-based polyol can be a polyol compound represented by the following formula 2.
[0106] [Formula 1]
[0107]
[0108] [Formula 2]
[0109]
[0110] In Formula 1 and Formula 2, X is a dicarboxylic acid-derived unit, Y is a polyol-derived unit such as a triol or diol unit, and n and m are arbitrary numbers.
[0111] Here, the dicarboxylic acid-derived unit is a unit formed by conducting a urethane reaction of a dicarboxylic acid with a polyol compound, and the polyol compound-derived unit is a unit formed by conducting a urethane reaction of a polyol compound with a dicarboxylic acid or caprolactone.
[0112] That is, when the hydroxyl group of the polyol compound reacts with the carboxyl group of the dicarboxylic acid, water (H2O) molecules are released through a condensation reaction, and an ester bond is formed at the same time, wherein X in the above formula 1 means the portion other than the ester bond portion after the dicarboxylic acid forms an ester bond through a condensation reaction, Y also means the portion other than the ester bond after the polyol compound forms an ester bond through a condensation reaction, and the ester bond is represented in Formula 1.
[0113] In addition, Y of Formula 2 also represents a portion other than the ester bond after the polyol compound forms an ester bond with caprolactone.
[0114] Meanwhile, here, when the polyol compound-derived unit Y is a unit derived from a polyol compound including three or more hydroxyl groups, such as a triol unit, a structure in which the Y portion is branched in the structure of the above formula may be achieved.
[0115] The type of the dicarboxylic acid-derived unit X in Formula 1 is not particularly limited, but in order to ensure desired physical properties, it may be any one unit selected from the following: phthalic acid unit, isophthalic acid unit, terephthalic acid unit, trimellitic acid unit, tetrahydrophthalic acid unit, hexahydrophthalic acid unit, tetrachlorophthalic acid unit, oxalic acid unit, adipic acid unit, azelaic acid unit, sebacic acid unit, succinic acid unit, malic acid unit, glutaric acid unit, malonic acid unit, pimelic acid unit, suberic acid unit, 2,2-dimethylsuccinic acid unit, 3,3-dimethylglutaric acid unit, 2,2-dimethylglutaric acid unit, maleic acid unit, fumaric acid unit, itaconic acid unit and fatty acid unit.
[0116] In Formula 1 and Formula 2, the type of unit Y derived from the polyol compound is not particularly limited, but it can be any one or two or more selected from the following: ethylene glycol unit, propylene glycol unit, 1,2-butanediol unit, 2,3-butanediol unit, 1,3-propanediol unit, 1,3-butanediol unit, 1,4-butanediol unit, 1,6-hexanediol unit, neopentyl glycol unit, 1,2-ethylhexyl glycol unit, 1,5-pentanediol unit, 1,10-decanediol unit, 1,3-cyclohexanedimethanol unit, 1,4-cyclohexanedimethanol unit, glycerol unit and trimethylolpropane unit.
[0117] In Formula 1, n is an arbitrary number and its range may be selected in consideration of desired physical properties, for example, it may be approximately 2 to 10 or 2 to 5. In Formula 2, m is an arbitrary number and its range may be selected in consideration of desired physical properties, for example, it may be approximately 1 to 10 or 1 to 5.
[0118] In the curable composition mixed with the main part according to one example of the present application, the lower limit of the weight ratio of the polyol compound in the main part relative to the total weight of the main part can be 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, 4.5 wt%, 5 wt%, 5.5 wt%, 6 wt%, 6.5 wt%, 7 wt%, 7.5 wt%, 8 wt%, 8.5 wt%, or 9.5 wt%, and the upper limit thereof can be 20 wt%, 18 wt%, 16 wt%, 14 wt%, 12 wt%, or 10 wt%. The ratio can be in the range of greater than or equal to, or greater than any one of the above lower limits; in the range of less than or equal to, or less than any one of the above upper limits; or in the range of less than or equal to, or less than any one of the above upper limits and greater than or equal to, or greater than any one of the above lower limits. When the polyol compound is adjusted to the above content ratio, after being partially combined with the curing agent, a cured product having excellent surface hardness can be ensured.
[0119] In the curable composition mixed with the main part according to an example of the application, as required during the process, the main part can also include filler components. Filler components can be thermally conductive fillers, and can use as required one or two or more as appropriately selected, wherein shape or ratio are not particularly limited, it can consider the viscosity of the main part, with the possibility of sedimentation in the cured product after the curing agent part combination, the heat resistance or thermal conductivity, insulation, filling effect or dispersibility etc. of the desired selected. In addition, even if the filler of the same type is used, it is also possible to mix and use those with different shapes, and it is also possible to mix and use those with different average grain sizes. For example, a mixture of aluminum hydroxide, aluminum and aluminum oxide can be used, and their respective shapes and average grain sizes can be different.
[0120] In the curable composition mixed with the main part according to one example of the present application, the filler component of the main part can be, for example, an oxide filler, such as aluminum oxide (aluminum oxide), magnesium oxide, beryllium oxide or titanium oxide; a nitride filler, such as boron nitride, silicon nitride or aluminum nitride; a carbide filler, such as silicon carbide; a hydroxide filler, such as aluminum hydroxide or magnesium hydroxide; a metal filler, such as copper, silver, iron, aluminum or nickel; a metal alloy filler, such as titanium; a silicon powder, such as quartz, glass or silicon dioxide; or a carbon filler, such as graphite or activated carbon, but is not limited thereto.
[0121] In a curable composition mixed with a main part according to an example of the present application, the lower limit of the weight ratio of the filler component in the main part relative to 100 parts by weight of the polyol compound can be 500 parts by weight, 600 parts by weight, 700 parts by weight, 800 parts by weight, or about 900 parts by weight, and the upper limit thereof can be about 2,000 parts by weight, 1,500 parts by weight, or 1,000 parts by weight. The ratio can be in a range greater than or equal to, or greater than any one of the above lower limits; in a range less than or equal to, or less than any one of the above upper limits; or in a range less than or equal to, or less than any one of the above upper limits and greater than or equal to, or greater than any one of the above lower limits. When the content of the polyol compound and the filler component is adjusted to the above ratio, after combining with the curing agent part, a cured product with excellent surface hardness and thermal conductivity can be ensured.
[0122] In the curable composition mixed with the main part according to one example of the present application, the filler component of the main part may include one or more selected from the first filler, the second filler and the third filler. The first filler to the third filler each have a different average particle size.
[0123] The lower limit of the average particle size of the first filler component can be about 60 μm, 61 μm, 62 μm, 63 μm, 64 μm, 65 μm, 66 μm, 67 μm, 68 μm, 69 μm, or 70 μm, and the upper limit thereof can be about 200 μm, 190 μm, 180 μm, 170 μm, 160 μm, or 150 μm. The average particle size can be in a range greater than or equal to, or greater than any of the above lower limits; in a range less than or equal to, or less than any of the above upper limits; or in a range less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.
[0124] The lower limit of the average particle size of the second filler may be about 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, or 20 μm, and the upper limit thereof may be about 58 μm, 56 μm, 54 μm, 52 μm, 50 μm, 48 μm, 46 μm, 44 μm, 42 μm, or 40 μm. The average particle size may be in a range greater than or equal to, or greater than any of the above lower limits; in a range less than or equal to, or less than any of the above upper limits; or in a range less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.
[0125] The upper limit of the average particle size of the third filler may be about 10 μm, 9 μm, 8 μm, 7 μm, 6 μm, 5 μm, 4 μm, 3 μm, or 2 μm, and the upper limit thereof may be about 0.01 μm, 0.05 μm, 0.1 μm, or 0.5 μm. The average particle size may be in a range greater than or equal to, or greater than any of the above lower limits; in a range less than or equal to, or less than any of the above upper limits; or in a range less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.
[0126] The first filler may be a hydroxide filler. In addition, the second filler and the third filler may each independently be one or more fillers selected from oxide fillers, nitride fillers, carbide fillers, metal fillers, alloy fillers, silicon powders, and carbon fillers. By selecting the first filler component, the second filler component, and the third filler component from the types listed above and adjusting the average particle size ratio and / or weight ratio, appropriate thixotropy and viscosity can be ensured during the process, and a cured product with excellent thermal conductivity can be formed after partially mixing with the curing agent later.
[0127] In a curable composition mixed with a main part according to an example of the present application, when the filler component of the main part includes a first filler component and a second filler component at the same time, the lower limit of the average particle size ratio (DMF1 / DMF2) of the first filler component (DMF1) to the second filler component (DMF2) can be 1, 1.2, 1.4, 1.6, 1.8, 2, 2.2, 2.4, 2.6, 2.8, 3, 3.2, or 3.4, and the upper limit thereof can be 5, 4.8, 4.6, 4.4, 4.2, 4, 3.8, or 3.6. The ratio can be in a range greater than or equal to, or greater than any one of the above lower limits; in a range less than or equal to, or less than any one of the above upper limits; or in a range less than or equal to, or less than any one of the above upper limits and greater than or equal to, or greater than any one of the above lower limits. By satisfying the above ratios, appropriate thixotropy and viscosity can be ensured during the process.
[0128] In addition, in the curable composition mixed with the main part according to one example of the present application, when the filler component of the main part includes both the first filler component and the second filler component, the weight ratio (MF1 / MF2) of the first filler component (MF1) to the second filler component (MF2) may have a lower limit of about 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, or 0.7, and an upper limit thereof may be about 5, 4.5, 4, 3.5, 3, 2.5, 2, 1.5, 1, or 0.75. The ratio may be in a range of greater than or equal to, or greater than any of the above lower limits; in a range of less than or equal to, or less than any of the above upper limits; or in a range of less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits.
[0129] By satisfying the above ratio, appropriate thixotropy and viscosity can be ensured during the process.
[0130] In the curable composition mixed with the main part according to one example of the present application, when the filler component of the main part includes both the first filler component and the third filler component, the lower limit of the average particle size ratio (DMF1 / DMF3) of the first filler component (DMF1) to the third filler component (DMF3) may be about 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, or 30, and the upper limit thereof may be about 50, 49, 48, 47, 46, 45, 44, 43, 42, 41, 40, 39, 38, 37, 36, or 35. The ratio may be in the range of greater than or equal to, or greater than any of the above lower limits; in the range of less than or equal to, or less than any of the above upper limits; or in the range of less than or equal to, or less than any of the above upper limits and greater than or equal to, or greater than any of the above lower limits. By satisfying the above ratio, appropriate thixotropy and viscosity can be ensured during the process.
[0131] In the curable composition mixed with the main part according to one example of the present application, when the filler component of the main part includes the first filler component and the third filler component at the same time, the weight ratio (MF1 / MF3) of the first filler component (MF1) to the third filler component (MF3) may be 0.5, 0.6, 0.7, 0.8, 0.9, or about 1, and the upper limit thereof may be about 10, 8, 6, 4, or 2. The ratio may be in a range greater than or equal to, or greater than any of the above lower limits; in a range less than or equal to, or less than any of the above upper limits; or in a range less than or equal to, or less than any of the above upper limits while greater than or equal to, or greater than any of the above lower limits. By satisfying the above ratio, appropriate thixotropy and viscosity may be ensured during the process.
[0132] In the curable composition mixed with the main part according to an example of the present application, the main part may also include additives, wherein the additives may include one or more selected from the following: curing delay agent, catalyst, plasticizer, flame retardant, thixotropy imparting agent, diluent, surface treatment agent, coupling agent and dispersant. If the curing delay agent can delay the curing of the main part, those used in the art can be used without restriction, for example, 1-dodecyl mercaptan etc. can be used. In addition, if when the main part and the curing agent part are combined, the catalyst can promote the curing reaction, those used in the art can be used without restriction, for example, dibutyltin dilaurate can be used.
[0133] The curable composition mixed with the main part according to an example of the present application can be used by mixing the main part and the curing agent part with a suitable volume ratio. Volume ratio means the ratio (B / A) of the volume (B) of the curing agent part to the volume (A) of the main part. For example, the lower limit of the ratio B / A can be about 0.01, 0.05, 0.1, 0.5, 1, 10, 50 or 100, and its upper limit can be about 200, 150, 100, 50, 40, 30, 20, 10, 9, 8, 7, 6, 5, 4, 3, 2, 1, 0.5, 0.1, 0.05 or 0.01. Ratio can be greater than or equal to or greater than the scope of any one of the above-mentioned lower limit; In the range of less than or equal to or less than any one of the above-mentioned upper limit; Or in the range of less than or equal to or less than any one of the above-mentioned upper limit, greater than or equal to or greater than any one of the above-mentioned lower limit at the same time.
[0134] The curable composition mixed with the main part according to an example of the present application can be cured to form a cured product, and can have at least one or more of the following physical properties. Each physical property as listed below is independent, wherein one physical property does not take precedence over other physical properties, and the cured product can satisfy at least one or two or more of the physical properties as listed below. The cured product of the curable composition mixed with the main part according to an example of the present application that satisfies at least one or two or more of the following physical properties is produced by the combination of each component.
[0135] The lower limit of the thermal conductivity of the cured product of the curable composition mixed with the main part according to one example of the present application may be about 3.0, 3.05, or 3.1, and the upper limit thereof may be about 20 W / m·K, 18 W / m·K, 16 W / m·K, 14 W / m·K, 12 W / m·K, 10 W / m·K, 8 W / m·K, 6 W / m·K, or 4 W / m·K. The thermal conductivity may be in a range greater than or equal to, or greater than any one of the above lower limits; in a range less than or equal to, or less than any one of the above upper limits; or in a range less than or equal to, or less than any one of the above upper limits and greater than or equal to, or greater than any one of the above lower limits. In a state where the cured product is manufactured as a sample (cured product) with a thickness of 20 mm, the thermal conductivity may be measured along the thickness direction of the sample according to the ASTM D5470 standard or the ISO 22007-2 standard.
[0136] The lower limit of the surface hardness of the cured product of the curable composition mixed with the main part according to an example of the present application can be about 50, 55, 60, 65, 70, 75, or 80 in Shore A hardness, and the upper limit can be about 80, 75, 70, 65, 60, or 55 in Shore D hardness, or can be about 100, 95, or 90 in Shore A hardness. The hardness can be greater than or equal to, or greater than any one of the above lower limits; or less than or equal to, or less than any one of the above upper limits and greater than or equal to, or greater than any one of the above lower limits. The hardness can be measured according to the ASTM D2240 standard, and the specific method is summarized in the embodiments of this specification.
[0137] The cured product of the curable composition mixed with the main part according to one example of the present application can ensure durability for products such as automobiles that require a long warranty period (about 15 years or longer in the case of automobiles). Durability can mean that it will not fall off or peel off from the module housing or battery cell of the battery module, or cracks will not appear after repeating 100 cycles of thermal shock testing, one of which includes keeping the temperature at a low temperature of about -40°C for 30 minutes, then raising the temperature to 80°C and keeping it for 30 minutes.
[0138] The cured product of the curable composition mixed with the main part according to an example of the application can have 10kV / mm or larger, 15kV / mm or larger or 20kV / mm or larger electrical insulation characteristics. Because the dielectric breakdown voltage has a higher value, the cured product of the curable composition mixed with the main part according to an example of the application shows excellent insulation characteristics, which can be about 50kV / mm or less, 45kV / mm or less, 40kV / mm or less, 35kV / mm or less or 30kV / mm or less, but is not particularly limited. In order to realize such dielectric breakdown voltage, insulating filler can be applied to the curable composition mixed with the main part according to an example of the application. Usually, in thermally conductive fillers, known ceramic fillers are used as components that can ensure insulation characteristics. Electrical insulation characteristics can be measured by the dielectric breakdown voltage measured according to ASTM D149 standards. In addition, if the cured product of the curable composition mixed with the main part according to one example of the present application can ensure such electrical insulation properties, stability can be ensured while maintaining excellent performance of various materials such as a housing or battery cell included in a battery module.
[0139] The volume resistance of the cured product of the curable composition mixed with the main part according to one example of the present application may be 1×10 10 Ω·cm or more, 3×10 10 Ω·cm or more, 7×10 10 Ω·cm or more, or 9×10 10 Ω·cm or more, and in another example, the volume resistance of the cured product of the curable composition mixed with the main part according to one example of the present application may be 1×10 14 Ω·cm or less, 7.5×10 13 Ω·cm or less, 5×10 13 Ω·cm or less, 2.5×10 13 Ω·cm or less, or 1×10 13Ω·cm or less. Here, the volume resistance of the cured product of the curable composition mixed with the main part according to one example of the present application can be within the range formed by appropriately selecting the upper and lower limits as listed above. The volume resistance can be measured by a volume resistance measuring device using a cured product of a curable composition mixed with the main part according to one example of the present application with a thickness of 0.2cm according to the ASTM D257 standard. If the cured product of the curable composition mixed with the main part according to one example of the present application can ensure such a volume resistance, excellent electrical insulation properties can be ensured, so that when it is used for various materials such as the housing or battery cell of a battery module, etc., stability can be ensured while maintaining performance.
[0140] The specific gravity of the cured product of the curable composition mixed with the main part according to an example of the application can be 5 or less. In another example, specific gravity can be 4.5 or less, 4 or less, 3.5 or less or 3 or less. Because the specific gravity of the cured product of the curable composition mixed with the main part according to an example of the application has a lower value, it is more conducive to the reduction of the weight of the applied product, so that its lower limit is not particularly limited. For example, specific gravity can be about 1 or more or 1.2 or more.
[0141] It is suitable that the cured product of the curable composition mixed with the main part according to an example of the present application does not contain volatile substances as much as possible.For example, the cured product of the curable composition mixed with the main part according to an example of the present application can have a non-volatile component ratio of 90 weight % or more, 95 weight % or more, or 98 weight % or more.Here, the ratio of non-volatile components can be defined in the following manner.That is, non-volatile content can be defined as the remaining part after the cured product of the curable composition mixed with the main part according to an example of the present application is kept at 100 ° C for about 1 hour, so the ratio can be based on the initial weight of the cured product of the curable composition mixed with the main part according to an example of the present application and the ratio of the weight after it is kept at 100 ° C for about 1 hour to measure.
[0142] The cured product of the curable composition mixed with the main part according to one example of the present application will have excellent degradation resistance as required, and may need to be as chemically non-reactive as possible.
[0143] It may be advantageous for the cured product of the curable composition mixed with the main part according to an example of the present application to have a low shrinkage during or after curing. Thus, the occurrence of stratification or gaps that can occur during the manufacture or use process of various materials (such as the housing or battery cell included in the battery module, etc.) can be prevented. The shrinkage can be appropriately adjusted within the range that can show the above effect, and may be, for example, less than 5%, less than 3%, or less than about 1%. When the shrinkage has a lower value, it is more advantageous so that its lower limit is not particularly limited.
[0144] It may also be advantageous that the cured product of the curable composition mixed with the main part according to an example of the present application has a low coefficient of thermal expansion (CTE). Thus, the occurrence of stratification or voids that can occur during the manufacture or use process of various materials (such as the housing or battery cell included in the battery module, etc.) can be prevented. The thermal expansion coefficient can be appropriately adjusted within the range that can express the above-mentioned effect, and may be, for example, less than 300ppm / K, less than 250ppm / K, less than 200ppm / K, less than 150ppm / K or less than 100ppm / K. When the thermal expansion coefficient has a lower value, it is more advantageous so that its lower limit is not particularly limited.
[0145] The tensile strength of the cured composition mixed with the main part according to one example of the present application can be appropriately adjusted, and thereby, excellent impact resistance, etc. can be ensured. The tensile strength can be adjusted, for example, within a range of about 1.0 MPa or more.
[0146] In the cured product of the curable composition mixed with the main part according to one example of the present application, the 5% weight loss temperature in the thermogravimetric analysis (TGA) may also be 400°C or higher, or the remaining amount at 800°C may be 70 wt% or more. Due to these characteristics, the stability at high temperatures can be further improved for various materials such as a housing or battery cell included in a battery module. In another example, the remaining amount at 800°C may be about 75 wt% or more, about 80 wt% or more, about 85 wt% or more, or about 90 wt% or more. In another example, the remaining amount at 800°C may be about 99 wt% or less. Thermogravimetric analysis (TGA) can be performed at 60 cm 3 / minute nitrogen (N2) atmosphere with a heating rate of 20 ° C / minute in the range of 25 ° C to 800 ° C. Thermogravimetric analysis (TGA) results can also be achieved by adjusting the composition of the cured product of the curable composition mixed with the main part according to an example of the present application. For example, the remaining amount at 800 ° C depends on the type or ratio of the thermally conductive filler contained in the cured product of the curable composition mixed with the main part according to an example of the present application, and when an excess of thermally conductive filler components is included, the remaining amount increases. However, when the polymer and / or monomer used in the curable composition mixed with the main part according to an example of the present application generally has high heat resistance compared with other polymers and / or monomers, the remaining amount increases more, and the polymer and / or monomer components contained in the cured product of the curable composition mixed with the main part according to an example of the present application also affect the hardness.
[0147] The curable composition mixed with the main part according to one example of the present application can be formed by mixing the components listed above. In addition, if all necessary components can be included, the curable composition mixed with the main part according to one example of the present application has no particular limitation on the mixing order.
[0148] The curable composition mixed with the main part according to an example of the present application using the curable composition of the present application can be used for various electrical and electronic products, such as irons, washing machines, drying machines, clothes managers (clothesmanager), electric shavers, microwave ovens, electric ovens, rice cookers, refrigerators, dishwashers, air conditioners, fans, humidifiers, air purifiers, mobile phones, wireless telegraphs, television sets, radios, computers and portable computers or batteries such as secondary batteries, so that the heat generated is dissipated. Especially, in the electric vehicle battery manufactured by assembling battery cells to form a battery module and combining several battery modules to form a battery pack, curable composition can be used as the material for connecting battery cells or battery modules. When curable composition is used as the material for connecting battery cells or battery modules, it can be used for dissipating the heat generated in the battery cells and fixing the battery cells to avoid external shocks and vibrations.
[0149] The cured product of the curable composition mixed with the main part according to one example of the present application can transfer the heat generated by the heating element (such as a heating element) to the cooling area. That is, the cured product of the curable composition mixed with the main part according to one example of the present application can dissipate the heat generated by the heating element. Here, the heating element can be a battery cell or a battery module.
[0150] The cured product of the curable composition mixed with the main part according to one example of the present application can be positioned between the heating element and the cooling area so that they are in thermal contact. Thermal contact means that the cured product of the curable composition mixed with the main part according to one example of the present application is in direct physical contact with the heating element and the cooling area so that the heat generated by the heating element is dissipated to the cooling area, or even if the cured product of the curable composition mixed with the main part according to one example of the present application is not in direct contact with the heating element and the cooling area (i.e., there is a separate layer between the cured product of the curable composition mixed with the main part according to one example of the present application and the heating element and / or the cooling area), it also dissipates the heat generated by the heating element to the cooling area.
[0151] Beneficial Effects
[0152] The application can provide such curable composition and its purposes, the curable composition is conducive to the reduction of weight by showing low density, and has excellent retention stability and storage stability by suppressing viscosity change over time. In addition, the curable composition can show excellent blending characteristics during the manufacturing process, and forms a cured product with high thermal conductivity, low specific gravity (density) and relatively high hardness when solidified. The application can also provide a device comprising a curable composition or its cured product. DETAILED DESCRIPTION
[0153] Hereinafter, the present application will be described through Examples and Comparative Examples, but the scope of the present application is not limited to the contents presented below.
[0154] 1. Viscosity measurement
[0155] The viscosity of the curable composition was measured using a viscometer (manufacturer: Brookfield, model name: DV3T Rheometer) and a spindle CPA-52Z. The spindle was rotated at a shear rate of about 1.2 rpm for about 180 seconds at room temperature (about 25°C), and the last measured value was regarded as the measured viscosity.
[0156] The plate is mounted on the plate connection of the viscometer, and the distance between the spindle and the plate is adjusted using a control rod. After separating the plate, about 0.5 mL of the sample (curable composition) is applied to the center of the plate, and then the plate is mounted on the plate connection of the viscometer again. After waiting until the torque becomes 0, the spindle is rotated at a shear rate of 1.2 rpm for 180 seconds at room temperature (about 25°C), and the viscosity measured at the end is determined.
[0157] 2. Viscosity change rate measurement
[0158] The initial viscosity V of the curable composition is measured by the above viscosity measurement method. i . Initial viscosity Vi The initial viscosity V is the viscosity measured within about 10 minutes from the time when the curable composition is prepared. i The curable composition is kept at room temperature (about 25° C.) for about 240 hours, and then the viscosity V is measured by the above viscosity measurement method. f .
[0159] Then, by calculating the viscosity V i and V f Substituting into the following general equation 1 to obtain the viscosity change rate V R The viscosity measurement was performed on the curable composition whose blending characteristics were evaluated as PASS in the following blending characteristics evaluation method.
[0160] [General equation 1]
[0161] V R =100×|V f -V i | / V i
[0162] In the general equation 1, V i is the initial viscosity, and V f The initial viscosity V is measured i The viscosity of the curable composition is measured after being kept at room temperature (about 25° C.) for 240 hours.
[0163] 3. Density measurement
[0164] The curable composition was completely filled into a 10 mL vial using a pneumatic dispenser. The weight (W1, unit: g) of the vial containing the curable composition was measured at room temperature (about 25° C.), and as the weight of the vial measured at room temperature (about 25° C.), the weight (W2, unit: g) of the empty vial before filling the curable composition was also measured. The weight W3 (g) obtained by subtracting the weight W2 (g) from the weight W1 (g) was divided by 10 mL to obtain a density (W3 / 10, unit: g / mL).
[0165] 4. Evaluation of blending properties
[0166] The blending characteristics of the curable compositions were evaluated based on the following criteria.
[0167] <Blending Characteristics Evaluation Criteria>
[0168] PASS: Determines the state in which the prepared curable composition has a smooth surface without any agglomeration of filler when observed with the naked eye
[0169] NG: Determine the case where, when the prepared curable composition is observed with the naked eye, it has a state of having a rough surface due to agglomeration of the filler
[0170] 5. Shore A hardness measurement
[0171] The curable composition obtained by mixing each curable composition prepared in the embodiment or comparative example with the main part of Preparation Example 1 in a volume ratio of 1: 1 was injected into a disc-shaped silicone mold having a diameter of 50 mm and a thickness of 20 mm, and kept at room temperature (about 25° C.) for about 24 hours to prepare a cured product. The Shore A hardness of the surface of the cured product was measured at room temperature (about 25° C.) using a hardness meter (Shore A hardness meter) according to the ASTM D2240 standard. The surface of the cured product in a flat state was pierced with an indenter capable of measuring the Shore A hardness of a hardness meter (manufacturer: TQCSheen, product name: LD0550), and the hardness was then measured while maintaining the piercing force.
[0172] 6. Thermal conductivity measurement
[0173] Thermal conductivity was measured using the hot disk method. The curable composition obtained by mixing each curable composition prepared in the embodiment or comparative example with the main part of Preparation Example 1 in a volume ratio of 1:1 was injected into a disk-shaped silicone mold having a diameter of 50 mm and a thickness of 20 mm, and kept at room temperature (about 25°C) for about 24 hours to prepare a cured product. Thermal conductivity was measured along the thickness direction of the cured material using a thermal conductivity measuring device (manufacturer: Hot disk, product name: TPS-2200) according to ISO 22007-2 standard.
[0174] 7. Average particle size measurement
[0175] The average particle size of the filler mentioned in this specification is the D50 particle size, also referred to as the so-called median particle size, which is the particle size at the cumulative 50% of the volume-based cumulative curve of the particle size distribution. Such a particle size can be defined as the particle size at the point where the cumulative value is 50% in the cumulative curve in which the particle size distribution is obtained based on volume and the total volume is set to 100%. The D50 particle size can be measured using the MASTERSIZER 3000 device of Marven according to ISO-13320, using ethanol as a solvent.
[0176] 8.Packing shape measurement
[0177] The sphericity of a filler can be defined as the ratio (S' / S) of the surface area (S) of a particle and the surface area (S') of a sphere having the same volume as the particle. For actual particles, circularity is generally used. Circularity is expressed as the ratio of the boundary (P) of an image obtained from a two-dimensional image of an actual particle and the boundary of a circle having the same area (A) as the area of the same image, and is obtained by the following equation.
[0178] <Circularity equation>
[0179] Circularity = 4πA / P 2
[0180] Circularity is expressed as a value from 0 to 1, with a perfect circle having a value of 1 and more irregularly shaped particles having values less than 1. In this specification, the sphericity value is taken as the average value of the circularity measured with Marvern's particle shape analysis equipment (FPIA-3000).
[0181] If the circularity thus measured is 0.9 or more, it is defined as a spherical filler, and if it is less than 0.9, it is defined as a non-spherical or rectangular filler.
[0182] Preparation Example 1. Main Part
[0183] A polyol compound (P), a catalyst (C), an aluminum oxide (FP1) (rectangular, average particle size: 1 μm to 2 μm) and an additive (AP) were mixed in a weight ratio of about 30:0.225:81.9:4.581 (P:C:FP1:AP) to prepare a primary mixture (Mx1), and primary stirring was performed with a slurry mixer under the conditions of 500 rpm in the revolution direction and 400 rpm in the spin direction until proper mixing was achieved. Alumina (FP2) (spherical, average particle size: 20 μm) was added to the primary mixture at a ratio of 109.2 parts by weight relative to 81.9 parts by weight of the aluminum oxide (FP1), and aluminum hydroxide (FP3) (rectangular, average particle size: 70 μm) was added to a container at a ratio of 81.9 parts by weight relative to 81.9 parts by weight of the aluminum oxide (FP1) to prepare a secondary mixture (Mx2). The secondary mixture (Mx2) was stirred with a slurry mixer at 500 rpm in the orbital direction and 400 rpm in the self-rotation direction until it was uniformly mixed, and defoamed at 500 rpm in the orbital direction and 150 rpm in the self-rotation direction to prepare a main part.
[0184] The weight ratio of the polyol compound (P), catalyst (C), aluminum oxide (FP1), aluminum oxide (FP2), aluminum hydroxide (FP3) and additive (AP) in the main part is about 30:0.225:81.9:109.2:81.9:4.581 (P:C:FP1:FP2:FP3:AP).
[0185] As the main part of the polyol compound (P), a caprolactone-based polyol (weight average molecular weight: about 860 g / mol) obtained by reacting 1,4-butanediol (1,4-BDol) and caprolactone (CL) at a ratio of 1:2.78 (1,4-BDol:CL) was used; as the catalyst (C), dibutyltin dilaurate was used; and as the additive (AP), an additive obtained by mixing a curing retarder (AP1), a dispersant (AP2) and a flame retardant (AP3) at a weight ratio of 0.381:0.351:3.750 (AP1:AP2:AP3) was used. As the curing retarder, 1-dodecyl mercaptan was used; as the dispersant, a phosphoric acid-modified polyester dispersant was used; and as the flame retardant, a flame retardant obtained by mixing a phosphorus-based liquid flame retardant (J1) and a phosphorus-based solid flame retardant (J2) at a weight ratio of 1:1.5 (J1:J2) was used.
[0186] Example 1.
[0187] (1) Preparation of curable composition (1)
[0188] An isocyanate compound (I), aluminum hydroxide (FI1) (rectangular, average particle size: 1 μm to 2 μm), a plasticizer (Pz) and an additive (AI) are placed in a container at a weight ratio of 30:54.6:1.5:6.852 (I:FI1:Pz:AI) to prepare a primary mixture (My1), and primary stirring is performed with a slurry mixer under the conditions of 500 rpm in the revolution direction and 400 rpm in the rotation direction until they are uniformly mixed. Aluminum hydroxide (FI2) (rectangular, average particle size: 70 μm) is added to the container at a ratio of 109.2 parts by weight relative to 54.6 parts by weight of aluminum hydroxide (FI1), and spherical aluminum oxide (FI3) (spherical, average particle size: 20 μm) is added to the container at a ratio of 109.2 parts by weight relative to 54.6 parts by weight of aluminum hydroxide (FI1), and then further mixed with the primary mixture (My1) to prepare a secondary mixture (My2). The secondary mixture (My2) was stirred with a slurry mixer at 500 rpm in the orbital direction and 400 rpm in the self-rotation direction until it was uniformly mixed, and then further defoamed at 500 rpm in the orbital direction and 150 rpm in the self-rotation direction to prepare a curable composition.
[0189] The curable composition comprises an isocyanate compound (I), aluminum hydroxide (FI1), aluminum hydroxide (FI2), spherical aluminum oxide (FI3), a plasticizer (Pz) and an additive (AI) in a weight ratio of 30:54.6:109.2:109.2:1.5:6.852 (I:FI1:FI2:FI3:Pz:AI).
[0190] As the isocyanate compound (I), a mixture of hexamethylene diisocyanate trimer and hexamethylene diisocyanate in a weight ratio of about 1:1 was used, and as a plasticizer, diisononyl phthalate (DINA) was used. As the additive (AI), an additive obtained by mixing a hygroscopic agent (AI1), a dispersant (AI2) and a flame retardant (AI3) in a weight ratio of 2.430:0.672:3.750 (AI1:AI2:AI3) was used. As a hygroscopic agent, a vinyl-containing siloxane compound was used; as a dispersant, a phosphoric acid-modified polyester dispersant was used; and as a flame retardant, a flame retardant obtained by mixing a phosphorus-based liquid flame retardant (J1) and a phosphorus-based solid flame retardant (J2) in a weight ratio of 1:1.5 (J1:J2) was used.
[0191] (2) Preparation of curable composition (2)
[0192] The main part (MP) of Preparation Example 1 and the curable composition (1) (curing agent part (HP)) were each placed in a 40 mL cylinder and mixed while fixing a static mixer, and then they were discharged at a volume ratio of 1:1 (MP:HP) using a pneumatic dispenser to prepare a curable composition (2).
[0193] Example 2.
[0194] (1) Preparation of curable composition (1)
[0195] An isocyanate compound (I), rectangular aluminum hydroxide (FI1) (rectangular, average particle size: about 1 μm to 2 μm), a plasticizer (Pz) and an additive (AI) are placed in a container at a weight ratio of 30:54.6:3.0:6.852 (I:FI1:Pz:AI) to prepare a primary mixture (My1), and primary stirring is performed with a slurry mixer under the conditions of 500 rpm in the revolution direction and 400 rpm in the rotation direction until they are uniformly mixed. Aluminum hydroxide (FI2) (rectangular, average particle size: about 70 μm) is added to the container at a ratio of 109.2 parts by weight relative to 54.6 parts by weight of aluminum hydroxide (FI1), and aluminum oxide (FI3) (spherical, average particle size: about 20 μm) is added to the container at a ratio of 109.2 parts by weight relative to 54.6 parts by weight of aluminum hydroxide (FI1), and then mixed with the primary mixture (My1) to prepare a secondary mixture (My2). The secondary mixture (My2) was stirred with a slurry mixer at 500 rpm in the orbital direction and 400 rpm in the self-rotation direction until it was properly mixed, and was further defoamed at 500 rpm in the orbital direction and 150 rpm in the self-rotation direction to prepare a curable composition (1).
[0196] The curable composition (1) comprises an isocyanate compound (I), aluminum hydroxide (FI1), aluminum hydroxide (FI2), aluminum oxide (FI3), a plasticizer (Pz) and an additive (AI) in a weight ratio of 30:54.6:109.2:109.2:3.0:6.852 (I:FI1:FI2:FI3:Pz:AI).
[0197] The isocyanate compound (I), plasticizer (Pz) and additive (AI) used are the same as those in Example 1.
[0198] (2) Preparation of curable composition (2)
[0199] The curable composition (1) was mixed with the main part in the same manner as in Example 1 to prepare a curable composition (2).
[0200] Comparative Example 1.
[0201] (1) Preparation of curable composition (1)
[0202] An isocyanate compound (I), aluminum oxide (FI4) (rectangular, average particle size: about 1 μm to 2 μm) and an additive (AI) are placed in a container at a weight ratio of 30:54.6:6.852 (I:FI1:AI) to prepare a primary mixture (My1), and primary stirring is performed with a slurry mixer under the conditions of 500 rpm in the revolution direction and 400 rpm in the rotation direction until they are properly mixed. Aluminum oxide (FI3) (spherical, average particle size: about 20 μm) is added to the container at a ratio of 109.2 parts by weight relative to 54.6 parts by weight of aluminum oxide (FI4), and aluminum oxide (FI5) (spherical, average particle size: about 70 μm) is added to the container at a ratio of 109.2 parts by weight relative to 54.6 parts by weight of aluminum oxide (FI4) to further mix with the stirred primary mixture (My1) to prepare a secondary mixture (My2). The secondary mixture (My2) was stirred with a slurry mixer at 500 rpm in the orbital direction and 400 rpm in the self-rotation direction until it was properly mixed, and then further defoamed at 500 rpm in the orbital direction and 150 rpm in the self-rotation direction to prepare a curable composition (2).
[0203] The curable composition comprises an isocyanate compound (I), aluminum oxide (FI4), aluminum oxide (FI3), aluminum oxide (FI5) and an additive (AI) in a weight ratio of 30:54.6:109.2:109.2:6.852 (I:FI4:FI3:FI5:AI). Here, the isocyanate compound (I) and the additive (AI) used are the same as those in Example 1.
[0204] (2) Preparation of curable composition (2)
[0205] The curable composition (1) was mixed with the main part in the same manner as in Example 1 to prepare a curable composition (2).
[0206] Comparative Example 2.
[0207] (1) Preparation of curable composition (1)
[0208] An isocyanate compound (I), aluminum hydroxide (FI1) (rectangular, average particle size: about 1 μm to 2 μm) and an additive (AI) are placed in a container in a weight ratio of 30:54.6:6.852 (I:FI1:AI) to prepare a primary mixture (My1), and primary stirring is performed with a slurry mixer at 500 rpm in the orbital direction and 400 rpm in the rotational direction until they are properly mixed. Rectangular aluminum hydroxide (FI2) (rectangular, average particle size: about 70 μm) was added to the container at a ratio of 13.65 parts by weight relative to 54.6 parts by weight of aluminum hydroxide (FI1), aluminum oxide (FI3) (spherical, average particle size: about 20 μm) was added to the container at a ratio of 109.2 parts by weight relative to 54.6 parts by weight of aluminum hydroxide (FI1), and aluminum oxide (FI5) (spherical, average particle size: about 70 μm) was added to the container at a ratio of 95.55 parts by weight relative to 54.6 parts by weight of aluminum hydroxide (FI1) to further mix with the stirred primary mixture (My1) to prepare a secondary mixture (My2). The secondary mixture (My2) was stirred with a slurry mixer under the conditions of 500 rpm in the revolution direction and 400 rpm in the self-rotation direction until it was properly mixed, and then further defoamed under the conditions of 500 rpm in the revolution direction and 150 rpm in the self-rotation direction to prepare a curable composition (1).
[0209] The curable composition (1) comprises an isocyanate compound (I), aluminum hydroxide (FI1), aluminum hydroxide (FI2), aluminum oxide (FI3), aluminum oxide (FI5) and an additive (AI) in a weight ratio of 30:54.6:13.65:109.2:95.55:6.852 (I:FI1:FI2:FI3:FI5:AI). The isocyanate compound (I) and the additive (AI) used are the same as those in Example 1.
[0210] (2) Preparation of curable composition (2)
[0211] The curable composition (1) was mixed with the main part in the same manner as in Example 1 to prepare a curable composition (2).
[0212] Comparative Example 3.
[0213] (1) Preparation of curable composition (1)
[0214] An isocyanate compound (I), aluminum hydroxide (FI1) (rectangular, average particle size: about 1 μm to 2 μm) and an additive (AI) are placed in a container in a weight ratio of 30:54.6:6.852 (I:FI1:AI) to prepare a primary mixture (My1), and primary stirring is performed with a slurry mixer at 500 rpm in the orbital direction and 400 rpm in the rotational direction until they are properly mixed. Aluminum hydroxide (FI2) (rectangular, average particle size: about 70 μm) was added to the container at a ratio of 68.25 parts by weight relative to 54.6 parts by weight of aluminum hydroxide (FI1), aluminum oxide (FI3) (spherical, average particle size: about 20 μm) was added to the container at a ratio of 109.2 parts by weight relative to 54.6 parts by weight of aluminum hydroxide (FI1), and spherical aluminum oxide (FI5) (spherical, average particle size: about 70 μm) was added to the container at a ratio of 40.95 parts by weight relative to 54.6 parts by weight of aluminum hydroxide (FI1) to further mix with the primary mixture (My1) to prepare a secondary mixture (My2). The secondary mixture (My2) was stirred with a slurry mixer under the conditions of 500 rpm in the revolution direction and 400 rpm in the self-rotation direction until it was properly mixed, and then a curable composition (1) was finally prepared through a defoaming process under the conditions of 500 rpm in the revolution direction and 150 rpm in the self-rotation direction.
[0215] The curable composition (1) comprises an isocyanate compound (I), aluminum hydroxide (FI1), aluminum hydroxide (FI2), aluminum oxide (FI3), aluminum oxide (FI5) and an additive (AI) in a weight ratio of 30:54.6:68.25:109.2:40.95:6.852 (I:FI1:FI2:FI3:FI5:AI). The isocyanate compound (I) and the additive (AI) used are the same as those in Example 1.
[0216] (2) Preparation of curable composition (2)
[0217] The curable composition (1) was mixed with the main part in the same manner as in Example 1 to prepare a curable composition (2).
[0218] Comparative Example 4.
[0219] (1) Preparation of curable composition
[0220] An isocyanate compound (I), aluminum hydroxide (FI1) (rectangular, average particle size: about 1 μm to 2 μm) and an additive (AI) are placed in a container at a weight ratio of 30:54.6:6.852 (I:FI1:AI) to prepare a primary mixture (My1), and primary stirring is performed with a slurry mixer under the conditions of 500 rpm in the revolution direction and 400 rpm in the rotation direction until they are properly mixed. Aluminum hydroxide (FI2) (rectangular, average particle size: about 70 μm) is added to the container at a ratio of 109.2 parts by weight relative to 54.6 parts by weight of aluminum hydroxide (FI1), and aluminum oxide (FI3) (spherical, average particle size: about 20 μm) is added to the container at a ratio of 109.2 parts by weight relative to 54.6 parts by weight of aluminum hydroxide (FI1) to further mix with the stirred primary mixture (My1) to prepare a secondary mixture (My2). The secondary mixture (My2) was stirred with a slurry mixer at 500 rpm in the orbital direction and 400 rpm in the self-rotation direction until it was properly mixed, and then a curable composition (1) was finally prepared through a defoaming process at 500 rpm in the orbital direction and 150 rpm in the self-rotation direction.
[0221] The curable composition (1) comprises an isocyanate compound (I), aluminum hydroxide (FI1), aluminum hydroxide (FI2), aluminum oxide (FI3) and an additive (AI) in a weight ratio of 30:54.6:109.2:109.2:6.852 (I:FI1:FI2:FI3:AI). The isocyanate compound (I) and the additive (AI) used are the same as those in Example 1.
[0222] (2) Preparation of curable composition (2)
[0223] The curable composition (1) was mixed with the main part in the same manner as in Example 1 to prepare a curable composition (2).
[0224] Comparative Example 5.
[0225] (1) Preparation of curable composition (1)
[0226] An isocyanate compound (I), aluminum hydroxide (FI1) (rectangular, average particle size: about 1 μm to 2 μm) and an additive (AI) are placed in a container at a weight ratio of 30:54.6:6.852 (I:FI1:AI) to prepare a primary mixture (My1), and primary stirring is performed with a slurry mixer under the conditions of 500 rpm in the revolution direction and 400 rpm in the rotation direction until they are properly mixed. Aluminum hydroxide (FI2) (rectangular, average particle size: about 70 μm) is added to the container at a ratio of 150.15 parts by weight relative to 54.6 parts by weight of aluminum hydroxide (FI1), and aluminum oxide (FI3) (spherical, average particle size: about 20 μm) is added to the container at a ratio of 95.55 parts by weight relative to 54.6 parts by weight of aluminum hydroxide (FI1) to further mix with the stirred primary mixture (My1), thereby preparing a secondary mixture (My2). The secondary mixture (My2) was stirred with a slurry mixer at 500 rpm in the revolution direction and 400 rpm in the rotation direction until it was properly mixed, and then a curable composition (1) was finally prepared by a defoaming process at 500 rpm in the revolution direction and 150 rpm in the rotation direction. The curable composition (1) comprises an isocyanate compound (I), aluminum hydroxide (FI1), aluminum hydroxide (FI2), aluminum oxide (FI3) and an additive (AI) in a weight ratio of 30:54.6:150.15:95.55:6.852 (I:FI1:FI2:FI3:AI). The isocyanate compound (I) and the additive (AI) used are the same as those in Example 1.
[0227] (2) Preparation of curable composition (2)
[0228] The curable composition (1) was mixed with the main part in the same manner as in Example 1 to prepare a curable composition (2).
[0229] Comparative Example 6.
[0230] (1) Preparation of curable composition (1)
[0231] An isocyanate compound (I), aluminum hydroxide (FI1) (rectangular, average particle size: about 1 μm to 2 μm), a plasticizer (Pz) and an additive (AI) are placed in a container at a weight ratio of 30:54.6:4.5:6.852 (I:FI1:Pz:AI) to prepare a primary mixture (My1), and primary stirring is performed with a slurry mixer under the conditions of 500 rpm in the revolution direction and 400 rpm in the rotation direction until they are properly mixed. Aluminum hydroxide (FI2) (rectangular, average particle size: about 70 μm) is added to the container at a ratio of 109.2 parts by weight relative to 54.6 parts by weight of aluminum hydroxide (FI1), and aluminum oxide (FI3) (spherical, average particle size: about 20 μm) is added to the container at a ratio of 109.2 parts by weight relative to 54.6 parts by weight of aluminum hydroxide (FI1) to further mix with the stirred primary mixture (My1), thereby preparing a secondary mixture (My2). The secondary mixture (My2) was stirred with a slurry mixer at 500 rpm in the orbital direction and 400 rpm in the self-rotation direction until it was properly mixed, and then a curable composition was prepared through a defoaming process at 500 rpm in the orbital direction and 150 rpm in the self-rotation direction.
[0232] The curable composition (1) comprises an isocyanate compound (I), aluminum hydroxide (FI1), aluminum hydroxide (FI2), aluminum oxide (FI3), a plasticizer (Pz) and an additive (AI) in a weight ratio of 30:54.6:109.2:109.2:4.5:6.852 (I:FI1:FI2:FI3:Pz:AI). The isocyanate compound (I), plasticizer (Pz) and additive (AI) used are the same as those in Example 1.
[0233] (2) Preparation of curable composition (2)
[0234] The curable composition (1) was mixed with the main part in the same manner as in Example 1 to prepare a curable composition (2).
[0235] The composition and content ratio of the curable composition (1) are shown in Table 1 below. In Table 1 below, FI1 is a rectangular aluminum hydroxide having an average particle size of about 1 μm to 2 μm, and FI2 is a rectangular aluminum hydroxide having an average particle size of about 70 μm. In addition, in Table 1 below, FI3 is a spherical aluminum oxide having an average particle size of about 20 μm, FI4 is a rectangular aluminum oxide having an average particle size of about 1 μm to 2 μm, and FI5 is a spherical aluminum oxide having an average particle size of about 70 μm.
[0236] [Table 1]
[0237]
[0238] The physical properties measured for the curable compositions of Examples and Comparative Examples are summarized in the following Table 2. In Table 2, the viscosity change rate, density and blending properties are for the curable composition (1) before mixing with the main part, and the Shore A hardness and thermal conductivity are for the curable composition mixed with the main part.
[0239] [Table 2]
[0240]
[0241] Referring to Table 2, it can be determined that the curable compositions of Examples 1 and 2 ensure a low viscosity change rate (V R ) (maintaining stability) and low density characteristics. In addition, referring to Table 2, it can be determined that the curable compositions of Examples 1 and 2 both have good blending characteristics and have desired levels of Shore A hardness and thermal conductivity.
[0242] On the other hand, it can be determined that the curable compositions of Comparative Examples 1 and 2 have too high a density, and that the curable compositions of Comparative Examples 3 and 4 exhibit too high a viscosity change rate (V R ), and the curable composition of Comparative Example 5 had poor blending characteristics, and thus the viscosity change rate (V R ). In addition, referring to Table 2, the curable composition of Comparative Example 6 cannot ensure thermal conductivity and Shore A hardness.
Claims
1. A curable composition comprising: Isocyanate compounds, Filler components, and Plasticizers, The curable composition has a density of 2.5 g / mL or less.
2. The curable composition according to claim 1, wherein V of the following general equation 1 R Is 15% or less: [General equation 1] V R =100×|V f -V i | / V i Where V i is the initial room temperature viscosity of the curable composition at a shear rate of 1.2 rpm, and V f is the room temperature viscosity of the curable composition measured at a shear rate of 1.2 rpm after the curable composition is kept at room temperature for 240 hours.
3. The curable composition of claim 1, wherein the filler component is present in an amount of 70 wt% to 95 wt% based on the total weight of the curable composition.
4. The curable composition of claim 1, wherein the filler component comprises a hydroxide filler.
5. The curable composition of claim 4, wherein the amount of the hydroxide filler in the filler component is from 30 wt% to 80 wt%. 6 . The curable composition according to claim 1 , wherein the filler component comprises a first hydroxide filler having an average particle size of 60 μm or more and a second hydroxide filler having an average particle size of 10 μm or less. 7 . The curable composition according to claim 6 , wherein a weight ratio of the first hydroxide filler to the second hydroxide filler is 0.1 to 10. 8 . The curable composition according to claim 6 , wherein a ratio of an average particle size of the first hydroxide filler to an average particle size of the second hydroxide filler is 10 to 100.
9. The curable composition of claim 4, wherein the filler component further comprises a non-hydroxide filler. 10 . The curable composition according to claim 9 , wherein the filler component comprises the non-hydroxide filler in an amount of 10 to 200 parts by weight relative to 100 parts by weight of the hydroxide filler.
11. The curable composition according to claim 1, wherein the plasticizer comprises one or more selected from the group consisting of phthalic acid compounds, phosphoric acid compounds, adipic acid compounds, sebacic acid compounds, citric acid compounds, glycolic acid compounds, trimellitic acid compounds, polyester compounds, epoxidized soybean oil, chlorinated paraffins, chlorinated fatty acid esters, fatty acid compounds, and vegetable oils. 12 . The curable composition according to claim 4 , wherein the amount of the plasticizer is 0.01 to 10 parts by weight relative to 100 parts by weight of the hydroxide filler.
13. The curable composition of claim 1, wherein the isocyanate compound comprises an aliphatic isocyanate compound. 14 . The curable composition according to claim 1 , wherein the isocyanate compound comprises a diisocyanate compound, and a polyisocyanate compound having trifunctionality or higher functionality.
15. A curable composition comprising: Contains a major portion of a polyol compound; and Curing agent part, wherein the curing agent portion comprises the curable composition according to claim 1.
16. The curable composition according to claim 15, wherein the curable composition is formulated to form a cured product having a thermal conductivity of 3 W / m·K or more according to ISO 22007-2 standard and having a Shore A hardness of 80 or more.
17. The curable composition of claim 15, wherein the polyol compound comprises a polyester polyol.
18. The curable composition of claim 15, wherein the major portion further comprises a filler component.
19. An apparatus comprising: Heating body; and Cooling area; as well as A cured product of the curable composition according to claim 15, The solidified product is in contact with the heat generating body and the cooling area.
20. A battery module, comprising: A cured product of the curable composition according to claim 15.
Citation Information
Patent Citations
System for Exchanging Heat between Waste Water Treatment Plant and Outside Plant
KR1020220064080A